Hot-dip galvanized steel sheet and its manufacturing method
Patent Information
- Application Number
- JP2024534742
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-09-27
- Filing Date
- 2024-01-23
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2044-01-23
Smart Images

Figure 0007635891000001 
Figure 0007635891000002 
Figure 0007635891000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot-dip galvanized steel sheet and a method for producing the same. [Background technology]
[0002] In recent years, surface-treated steel sheets that have been given rust-resistance, particularly hot-dip galvanized steel sheets (including alloyed hot-dip galvanized steel sheets) with excellent rust-resistance, have been widely used in the fields of automobiles, home appliances, building materials, etc. From the viewpoint of improving fuel efficiency and collision safety of automobiles, the application of high-strength steel sheets to automobile body materials is progressing in order to reduce the thickness by increasing the strength of the automobile body materials and to make the automobile body itself lighter and stronger. In general, hot-dip galvanized steel sheets are produced by using hot-rolled or cold-rolled steel sheets as base materials, subjecting the base steel sheets to recrystallization annealing in the annealing furnace of a CGL, and then subjecting them to hot-dip galvanizing. On the other hand, alloyed hot-dip galvanized steel sheets are produced by further subjecting the hot-dip galvanizing to alloying treatment.
[0003] In annealing, the steel sheet needs to be held in a reducing atmosphere containing hydrogen. At this time, hydrogen in the furnace penetrates into the steel sheet, and the steel sheet is then subjected to a cooling treatment and a hot-dip plating treatment, so that hydrogen remains in the steel sheet as diffusible hydrogen in steel. Since hydrogen is not permeable through plating, the diffusible hydrogen in steel is not released from the steel sheet after plating, and there was a problem that the delayed fracture resistance property is reduced when the amount of diffusible hydrogen in steel is large. In particular, in high-strength steel sheets with a tensile strength of 780 MPa or more, the diffusible hydrogen in steel is likely to remain after annealing, and there was a problem that the delayed fracture resistance property is significantly reduced. This is because in high-strength steel sheets with a tensile strength of 780 MPa or more, in order to obtain a specified strength, it is necessary to form a hard structure such as martensite or bainite, and for this purpose, it is necessary to generate an austenite phase in the annealing process, but the austenite phase is more likely to absorb a large amount of hydrogen than the ferrite phase, and the diffusion rate of hydrogen is slow, so once hydrogen is absorbed in the annealing process, it is difficult to release it in the cooling process. In recent years, there has been a tendency for such standards for delayed fracture resistance to become stricter.
[0004] Conventionally, as steel sheets having a reduced amount of hydrogen therein, for example, the following have been proposed. Patent Document 1 discloses a high-strength galvannealed steel sheet that has excellent delayed fracture resistance and hole expandability, and in which the amount of hydrogen released when the steel sheet is heated to 200°C is 0.35 mass ppm or less. Patent Document 2 discloses a high-strength galvanized steel sheet that has excellent plating properties and bendability and that releases hydrogen in an amount of 0.25 mass ppm or less when the steel sheet is heated to 210°C. Patent Document 3 discloses a high-strength galvanized steel sheet that has excellent plating properties and bendability, and has a tensile strength of 1,100 MPa or more, and in which the amount of hydrogen released when the steel sheet is heated to 210°C is 0.25 mass ppm or less. Furthermore, as a technique for producing a steel sheet having a reduced amount of hydrogen therein, for example, the following has been proposed. Patent Document 4 discloses a technique in which a hot-rolled steel sheet is subjected to a reduction treatment, then dehydrogenation treatment at 450 to 550° C. in an atmosphere with a H2 concentration of 8 to 20%, and then hot-dip galvanization is performed. Patent Document 5 discloses a technique for reducing the amount of hydrogen in a hot-rolled steel sheet by controlling the relationship between the annealing temperature in an annealing furnace and the hydrogen concentration to satisfy the following formula (1) in a method of reducing a hot-rolled steel sheet at a temperature in the range of 650 to 950°C and then hot-dip galvanizing the steel sheet. 1≦H≦-0.05×RT+57.5 (1) Here, H is the hydrogen concentration in the furnace and RT is the annealing temperature.
[0005] Patent Document 6 discloses a technique for obtaining good surface quality in a method for performing hot-dip galvanizing after reduction annealing of a steel sheet containing Si, Mn, and Al, by controlling the hydrogen concentration in a furnace during reduction annealing to be 10% by volume or more, and the relationship between the hydrogen partial pressure and the water vapor partial pressure in the furnace atmosphere gas at 650°C or more and less than 750°C to satisfy the following formula (2), and similarly controlling the relationship between the hydrogen partial pressure and the water vapor partial pressure in the furnace atmosphere gas at 750°C or more and 950°C to satisfy the following formula (3). log(P H2O / P H2 )≦-1.55 (2) -0.91≦log(P H2O / P H2 )≦-0.635 (3) [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2019 / 189067 [Patent Document 2] International Publication No. 2019 / 189849 [Patent Document 3] International Publication No. 2019 / 189841 [Patent Document 4] Japanese Unexamined Patent Publication No. 54-130443 [Patent Document 5] Patent No. 3266008 [Patent Document 6] Patent No. 5811841 Summary of the Invention [Problem to be solved by the invention]
[0007] However, with the techniques disclosed in Patent Documents 1, 2 and 3, it was difficult to achieve both strict delayed fracture resistance and good plating appearance quality. Furthermore, the techniques shown in Patent Documents 4 and 5 are both intended to suppress blisters (plating bulges) in hot-rolled steel sheets, and in order to improve the delayed fracture resistance of high-strength steel sheets having an austenitic phase in the annealing process, it is necessary to further reduce the amount of hydrogen in the atmosphere to reduce hydrogen in the steel. However, if the amount of hydrogen in the atmosphere is further reduced, the selective oxidation of easily oxidizable elements such as Si and Mn contained in the high-strength steel sheet is promoted, which inhibits galvanization and makes it impossible to obtain good surface quality. Therefore, it is difficult to improve good surface quality and delayed fracture resistance with the method of uniformly reducing hydrogen in the furnace as described in Patent Documents 4 and 5. In addition, the technology shown in Patent Document 6 aims to improve the galvanic properties of steel containing Si, Mn, and Al and to obtain good surface quality by changing the ratio of water vapor partial pressure to hydrogen partial pressure according to the annealing temperature. However, it is necessary to control the hydrogen concentration in the furnace to 10% or more, and no consideration is given to reducing the hydrogen concentration contained in the steel, so that it is difficult to improve the delayed fracture resistance of high-strength steel sheets.
[0008] Therefore, an object of the present invention is to solve the above-mentioned problems of the conventional art and to provide a manufacturing method by which a hot-dip galvanized steel sheet having high strength, a beautiful surface appearance free of uncoated areas, and excellent delayed fracture resistance can be manufactured.
[0009] Here, high strength refers to a steel plate having a tensile strength TS of 780 MPa or more when a tensile test is performed in accordance with JIS Z2241 (2011). A beautiful surface appearance without any uncoated areas refers to the fact that the appearance of the plating on a hot-dip galvanized steel sheet is visually observed, and for those that show patterns or irregularities, SEM observation is carried out and there are less than three uncoated defects within an area of 1 m x 1 m of the steel sheet. Excellent resistance to delayed fracture properties means that a rectangular test piece with a major axis length of 100 mm and a minor axis length of 20 mm is taken from a steel plate, a punched hole with a diameter of 15 mm and a clearance of 14.0% is formed at the center of the major and minor axes of this test piece, and the piece is subjected to a tensile test (tensile speed 10 mm / min). The load time in the tensile test is up to 100 hours, and the maximum stress at which no cracks occur after 100 hours of load is defined as the limit stress, and the limit stress / yield stress is 1.00 or more. The clearance was previously set at approximately 12.5%, but due to the recent trend towards stricter quality standards regarding delayed fracture resistance, stricter conditions have been adopted compared to the past. [Means for solving the problem]
[0010] The hydrogen concentration corresponding to the amount of hydrogen released at temperatures below 150°C when measured by temperature-programmed analysis is also the hydrogen concentration H H The inventors of the present invention have conducted extensive research to solve the above problems, and have found that the hydrogen concentration H H It was newly revealed that hydrogen is difficult to release into the atmosphere when the steel plate is held after production, but when it is processed, especially by pressing, it is transformed into diffusible hydrogen, which greatly affects the delayed fracture resistance. Furthermore, the hydrogen concentration H His trapped by a relatively weak force around inclusions contained in the steel sheet, such as MnS, Al2O3, (Al,Ca)-O, Nb(C,N), (Nb,Ti)(C,N) and Ti(C,S), and groups of inclusions in which MnS precipitates compositely around these inclusions as nuclei. The researchers have found that by optimizing the annealing and cooling atmosphere in the manufacturing method for galvanized steel sheet, in which these steel sheets (base steel sheets) are annealed and cooled before being hot-dip galvanized, it is possible to manufacture galvanized steel sheet with excellent coating appearance and resistance to delayed fracture.
[0011] The present invention has been made based on these findings, and the gist of the present invention is as follows. [1] In mass percent, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and 3.00% or less, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%) S: 0.0030% or less (excluding 0%) Sol.Al: 0.1% or less (excluding 0%) N: 0.0070% or less (excluding 0%) O: Contains 0.0030% or less (excluding 0%) Or even more so: Contains one or more of the following groups A, B, C, and D: Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the above, Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following, Group C Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more of the following: Group D Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following: A base steel sheet having a composition with the balance being Fe and unavoidable impurities; A zinc-based plating layer is formed on the surface of the base steel sheet, Furthermore, the inclusion group contained in the base steel sheet satisfies the following conditions (i) and (ii), and the inclusion group has a density of 10 pieces / mm 2 is as follows: The base steel sheet has a hydrogen content of 0.30 mass ppm or less at room temperature to 350°C and a hydrogen content of 0.20 mass ppm or less at 150 to 350°C, Within an area of 1m x 1m on the steel plate surface, there are less than three uncoated defects. Hot-dip galvanized steel sheet with a tensile strength of 780 MPa or more. (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When the inclusion group is composed of two or more of the inclusion particles, the major axis length of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less. [2] The hot-dip galvanized steel sheet according to [1], wherein the base steel sheet further contains, as the chemical composition, one or more groups selected from the following E, F, G and H groups, in mass %: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following [3] The hot-dip galvanized steel sheet according to [1] or [2], wherein the amount of hydrogen released from the base steel sheet at room temperature to 350°C is 0.20 ppm by mass or less, and the amount of hydrogen released at 150°C to 350°C is 0.15 ppm by mass or less. [4] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the total area ratio of martensite, bainite and retained austenite in the base steel sheet is 30% or more, and the tensile strength is 780 MPa or more. [5] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the total area ratio of martensite, bainite and retained austenite in the base steel sheet is 50% or more, and the tensile strength is 980 MPa or more. [6] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the total area ratio of martensite, bainite and retained austenite in the base steel sheet is 70% or more, and the tensile strength is 1180 MPa or more. [7] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the total area ratio of martensite, bainite and retained austenite in the base steel sheet is 85% or more, and the tensile strength is 1310 MPa or more. [8] The hot-dip galvanized steel sheet according to any one of [1] to [3], wherein the total area ratio of martensite, bainite and retained austenite in the base steel sheet is 90% or more, and the tensile strength is 1470 MPa or more. [9] The hot-dip galvanized steel sheet according to any one of [1] to [8], wherein the zinc-based coating layer is a galvannealed layer.
[10] A method for producing a hot-dip galvanized steel sheet, comprising annealing a base steel sheet and then applying hot-dip galvanizing, The base steel sheet comprises, in mass%, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and 3.00% or less, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%) S: 0.0030% or less (excluding 0%) Sol.Al: 0.1% or less (excluding 0%) N: 0.0070% or less (excluding 0%) O: Contains 0.0030% or less (excluding 0%) Or even more so: Contains one or more of the following groups A, B, C, and D: Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the above, Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following, Group C Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more of the following: Group D Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following: The balance is Fe and unavoidable impurities. Furthermore, the inclusion group contained in the base steel sheet satisfies the following conditions (i) and (ii), and the inclusion group has a density of 10 pieces / mm 2 is as follows: A first annealing process in which the base steel sheet is held at a holding temperature of 650°C to 950°C for 20 s to 150 s in an atmosphere having a dew point of -55°C to +30°C and a hydrogen concentration of 8.0 vol% to 25 vol%; A second annealing step of holding the base steel sheet that has been subjected to the first annealing step at a holding temperature of 700°C to 950°C for 30 s to 300 s in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 8.0 vol%; a cooling step in which the base steel sheet that has been subjected to the second annealing step is cooled in an atmosphere having a dew point of -20°C or lower and a hydrogen concentration of 0.2 volume% or more and 25 volume% or less from the holding temperature of 700°C or more and 950°C or less in the second annealing step to a temperature of 150°C or more and 550°C or less at an average cooling rate of 3 to 300°C / s; a hot-dip galvanizing process for performing a hot-dip galvanizing treatment on the base steel sheet after the cooling process to form a zinc-based plating layer on the surface of the base steel sheet; The present invention relates to a method for producing a hot-dip galvanized steel sheet having a tensile strength of 780 MPa or more, comprising the steps of: (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When the inclusion group is composed of two or more of the inclusion particles, the major axis length of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less.
[11] The method for producing a hot-dip galvanized steel sheet according to
[10] , wherein the base steel sheet further contains, as the chemical composition, one or more groups selected from the following groups E, F, G and H, in mass %: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following
[12] A method for producing a hot-dip galvanized steel sheet according to
[10] or
[11] , comprising an oxidation treatment step of subjecting the base steel sheet prior to the first annealing step to an oxidation treatment at a temperature of 400°C or higher and 900°C or lower in an atmosphere containing 1000 ppm by volume or more of O2.
[13] A method for producing a hot-dip galvanized steel sheet according to any one of
[10] to
[12] , comprising a reheating treatment step of holding the steel sheet at a temperature of 200°C or higher and 450°C or lower and in an atmosphere with a hydrogen concentration of 15% by volume or lower for a time of 5 s or higher and 600 s or lower after the hot-dip galvanized treatment, and then cooling the steel sheet.
[14] The method for producing a hot-dip galvanized steel sheet according to any one of
[10] to
[13] , wherein the atmosphere in the second annealing step has a hydrogen concentration of less than 5.0 volume %.
[15] The cooling step comprises: a first cooling step in which the base steel sheet that has been subjected to the second annealing step is cooled in an atmosphere having a dew point of -20°C or less and a hydrogen concentration of 0.2% by volume or more and less than 8.0% by volume in a temperature range from a holding temperature of 700°C or more and 950°C or less in the second annealing step to a steel sheet temperature of 650°C or less over a period of 10 s or more at an average cooling rate of 3°C / s or more and 25°C / s or less; a second cooling step of cooling the base steel sheet that has been subjected to the first cooling step in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 8.0% by volume or more and 25% by volume or less, from 600°C to a temperature of 150°C or more and 550°C or less at an average cooling rate of 10°C / s or more; The method for producing a hot-dip galvanized steel sheet according to any one of
[10] to
[14] , comprising:
[16] The method for producing a hot-dip galvanized steel sheet according to any one of
[10] to
[15] , further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer. Effect of the Invention
[0012] According to the present invention, there are provided a hot-dip galvanized steel sheet having high strength, a beautiful surface appearance free of uncoated areas, and excellent delayed fracture resistance, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] As one embodiment of the hot-dip galvanized steel sheet and its manufacturing method of the present invention, the manufacturing method of the hot-dip galvanized steel sheet and the hot-dip galvanized steel sheet will be described below in that order.
[0014] <Method of manufacturing hot-dip galvanized steel sheet> The method for producing a hot-dip galvanized steel sheet of the present invention is a method for producing a hot-dip galvanized steel sheet, comprising annealing a base steel sheet having a specific component composition described below, and then applying hot-dip galvanizing to the base steel sheet, The inclusion group contained in the base steel sheet satisfies the following conditions (i) and (ii), and the inclusion group is 10 pieces / mm 2 is as follows: a first annealing process in which the base steel sheet is held at a holding temperature of 650°C to 950°C for a period of 20 s to 150 s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 8.0 vol% to 25 vol%; and a second annealing process in which the base steel sheet that has undergone the first annealing process is held at a holding temperature of 700°C to 950°C for a period of 30 s to 300 s in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 8.0 vol%. The method includes a cooling process in which the base steel sheet that has undergone the second annealing process is cooled from the holding temperature of 700°C or more and 950°C or less in the second annealing process to a temperature of 150°C or more and 550°C or less at an average cooling rate of 3 to 300°C / s in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 0.2% by volume or more and 25% by volume or less, and a hot-dip galvanizing process in which the base steel sheet after the cooling process is subjected to a hot-dip galvanizing treatment to form a zinc-based plating layer on the surface of the base steel sheet. (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When an inclusion group is composed of two or more of the above-mentioned inclusion particles, the major axis length of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less.
[0015] Refining process In order to ensure excellent delayed fracture resistance, it is necessary to reduce impurity elements such as S, N, and O, and to reduce large inclusions in the refining process of molten steel. There are no particular limitations on the method for reducing impurity elements or large inclusions. For example, after oxygen blowing in a converter, the steel is tapped into a ladle, and the molten steel is desulfurized, and at the same time, the molten steel is vacuum degassed and refluxed using an RH vacuum degassing device to reduce the above-mentioned impurity elements and float and separate large inclusions of oxides containing Al and Ca (hereinafter also referred to as Al, Ca oxides), and then the molten steel is left to stand for a certain period of time to float and separate one layer of large inclusions, after which the molten steel is poured into a tundish. From the viewpoint of reducing large inclusions of Al and Ca oxides that may particularly deteriorate the delayed fracture resistance, it is preferable to circulate the molten steel in the RH vacuum degassing for more than 20 minutes. From the same viewpoint, it is also preferable to hold the molten steel for more than 10 minutes after the RH reflux treatment before pouring it into the tundish. By carrying out such treatment, it is possible to reduce large inclusions that deteriorate the delayed fracture resistance.
[0016] A more detailed explanation will be given below. In ores such as electrolytic Mn for Mn adjustment and raw ores such as ferrosilicon for Si adjustment, a certain amount of impurity components that form inclusions with a low melting point are contained. The low melting point inclusions generated by adding these ores to molten steel are stretched by hot rolling and crushed by cold rolling, and are distributed in a dotted line pattern. Such stretched inclusions or large inclusions distributed in a dotted line pattern have a large surface area compared to their volume and are poorly compatible with the steel sheet, so they are prone to occlude hydrogen in their surrounding areas during the annealing process before the hot-dip galvanizing process. Moreover, since the hydrogen absorbed around such inclusions is relatively strongly trapped, most of it is hydrogen that can be released at high temperatures of 150°C or higher, and is not easily diffused and released around room temperature. Therefore, the hydrogen absorbed around the inclusions is not easy to remove and is prone to remain in the steel sheet. Furthermore, the hydrogen remaining around the inclusions can become harmful hydrogen that causes cracks around the inclusions after press working. In addition, the origin of cracks is around large inclusions where stress is likely to concentrate, so cracks and fractures, especially delayed fractures, occur significantly after press working around large inclusions that trap hydrogen. In order to reduce such delayed fractures, it is desirable to reduce the distribution frequency of a group of large inclusions with a specific distribution pattern that are likely to absorb hydrogen during annealing and cause stress concentration during press working. Here, a group of large inclusions refers to a group of inclusions consisting of two or more inclusions that are close to each other.
[0017] The inclusion groups that have such a strong hydrogen absorption effect and are likely to cause delayed fracture after press working are as follows: The major axis length of each individual inclusion particle that makes up the inclusion group is 0.3 μm or more, when the inclusion group is composed of two or more inclusion particles, the shortest distance between the inclusion particles is 40 μm or less, and the major axis length of the inclusion group composed of the individual inclusions is 50 μm or more. Examples of inclusions that can form such inclusion groups include Al2O3, (Al,Ca)-O, MnS, Nb(C,N), (Nb,Ti)(C,N), Ti(C,S), etc. In particular, when inclusion groups containing coarse Al2O3 and (Al,Ca)-O inclusions with a maximum thickness (width in the plate thickness direction) of 4 μm or more are present, these inclusion groups significantly promote delayed fracture. In addition, the presence of Al2O3 and (Al,Ca)-O inclusions makes it easier for MnS and (Nb,Ti)(C,N) to precipitate in combination, which makes it easier to form even larger inclusions with a high frequency. Therefore, it is particularly important to reduce inclusion groups containing large oxide-based inclusions, and it is important to ensure a long circulation time in the above-mentioned RH vacuum degassing device and a stationary time before pouring the molten steel into the tundish. Other RH treatment conditions may be in accordance with established standards. For example, the gas pressure in the RH vacuum degassing apparatus may be about 50 to 1000 Pa, and the reflux gas may be 0.02 to 0.1 Nm 3 Argon gas with a flow rate of 800 kg / s can be used. The amount of molten steel to be processed can be 80 to 350 tons, and the reflux rate can be 800 to 3500 kg / s. From the viewpoint of suppressing the formation of MnS, Ti(C,S), it is desirable to reduce the amount of S, and from the viewpoint of suppressing the formation of Nb, Ti-based carbonitrides, it is desirable to reduce the amount of N.
[0018] Slab heating process Methods for hot rolling a steel slab include a method of rolling the slab after heating, a method of directly rolling the slab after continuous casting without reheating it, and a method of rolling the slab after continuous casting after subjecting it to a short-term heat treatment. In the manufacturing method of the present invention, the slab heating temperature is preferably set to more than 1220°C. By setting the slab heating temperature (surface temperature) to more than 1220°C, the solid solution of sulfides and carbonitrides is promoted and Mn segregation is reduced, thereby reducing the size and number of the above-mentioned inclusion group. Although there is no particular upper limit to the slab heating temperature, the slab heating temperature is preferably equal to or lower than 1400° C. In addition, the average heating rate during slab heating may be set to 5 to 15° C. / min.
[0019] It is preferable to hold the slab surface temperature at a temperature of more than 1220°C for 100 min or more. As a result of the investigation by the present inventors, it has become clear that the main reason why the inclusions remain is that even if the slab heating temperature reaches the melting temperature of the inclusions, if a sufficient soaking time is not ensured, the melting state does not reach equilibrium. By ensuring a sufficient soaking time, the solid solution of sulfides and carbonitrides is promoted, and the delayed fracture resistance is improved. If the holding time (soaking time) is less than 100 min, the solid solution of Nb and Ti-based carbonitrides becomes insufficient, and they remain, and MnS precipitates with them as nuclei, thereby deteriorating the delayed fracture resistance. The upper limit of the holding time (soaking time) is not particularly limited, but the holding time (soaking time) is preferably 250 min or less, more preferably 200 min or less. The holding time (soaking time) is further preferably 175 min or less.
[0020] Hot rolling process Here, the ratio ε2 / ε1 of the elongation strain of the long axis of the MnS-based inclusions as a group (the increase in the long axis including the increase in the distance between inclusions due to crushing, in the case of crushing) to the elongation strain of the steel calculated from the rolling reduction ratio: ε1 (the true strain when it is assumed that there is no change in the width direction) is 0.55 to 0.60 in hot rolling and 0.65 to 0.70 in cold rolling, and it was found that the inclusions are elongated in the rolling direction in both processes. This means that, compared with the reduction in hot rolling, a smaller reduction in cold rolling is effective in reducing the extensibility of inclusions, but the effect of adjusting the distribution of the reduction is very small, and that a smaller cumulative reduction is more effective in reducing the extensibility of inclusions. In other words, it is preferable to make the casting thickness of the slab thinner than the plate thickness of the final product plate. However, in reality, making the slab thinner impairs productivity, so the casting thickness of the slab is preferably in the range of 100 to 250 mm, and more preferably 150 to 200 mm. In addition, according to the established method, the cumulative reduction in the temperature range above 950°C is 70 to 98%, and the cumulative reduction at 950°C or less, including cold rolling, is 50 to 92%.
[0021] Finish rolling is preferably performed at a finish rolling temperature of 800 to 950°C, and then cooled to a temperature range of more than 400°C and not more than 630°C at a cooling rate of 10°C / s or more and not more than 200°C / s and coiled. The finish rolling temperature (FT) is preferably set to a range of 800 to 950°C from the viewpoint of promoting transformation, and is preferably set to a low temperature within a range not lower than the Ar3 transformation point. In the present invention, by setting the coiling temperature to 560°C or less, a fine ferrite + pearlite structure or a structure mainly composed of bainite can be obtained, and high strength can be ensured in the steel sheet after annealing thereafter, and the stability of strength in the coil is improved, and the thickness fluctuation of the steel sheet (coil) can be suppressed. In addition, by setting the coiling temperature to more than 400°C, hydrogen in the steel absorbed in the refining process can be sufficiently released, and the occurrence of cracks during cold rolling can be avoided, and this contributes to the reduction of hydrogen in the steel during the subsequent annealing. From the viewpoint of releasing hydrogen, the holding time of the coiled steel sheet at 350°C or more is set to 3000 seconds or more, and more preferably 5000 seconds or more. The holding time at 350°C or more is not particularly specified, but since special equipment or the like is required to hold the steel sheet at 350°C for a long period of time, the holding time is preferably 180000 seconds or less.
[0022] The wound coil is then removed from the coiler. At this time, the coil may be water-cooled while rotating if necessary, but in this case, it is preferable to keep the water-cooling time as short as possible. It is more preferable not to perform water-cooling. After winding the coil in a temperature range of more than 400°C and not more than 630°C, from the viewpoint of suppressing subsequent surface oxidation and uneven transformation, the coil may be water-cooled as is, or may be unwound and cooled with water or gas. Such a treatment is preferably performed after reducing hydrogen in the steel by holding the steel at 350°C or higher for a predetermined time.
[0023] It is also desirable to perform descaling to remove the primary and secondary scale formed on the steel sheet surface. Descaling is preferably performed at a high impact pressure of 50 MPa or more. This makes it possible to reduce the remaining red scale and the thickness of secondary scale formed, and to reduce surface oxidation of the steel sheet caused by oxygen in the scale being taken into the steel sheet during coiling in hot rolling. As a result, the thickness of the surface oxide layer in the final product can be reduced, improving corrosion resistance. It is preferable to thoroughly pickle the hot-rolled coil before cold rolling to reduce residual scale. From the viewpoint of reducing the load in cold rolling, the hot-rolled coil may be annealed as necessary.
[0024] Cold rolling process In cold rolling, the reduction rate (cumulative reduction rate) is set to 20-75%, and the thickness of the steel sheet after cold rolling is set to 0.5-3.2 mm, and other conditions may be in accordance with the established method. The lower limit of the reduction rate is preferably 30% or more, more preferably 40% or more. The upper limit of the reduction rate is preferably 72% or less, more preferably 70% or less. The thickness of the steel sheet after cold rolling is preferably 0.6 mm or more, more preferably 0.8 mm or more, and even more preferably 1.0 mm or more. The thickness of the steel sheet after cold rolling is preferably 2.8 mm or less, more preferably 2.3 mm or less, and even more preferably 2.0 mm or less.
[0025] Oxidation treatment, annealing, cooling, hot-dip galvanizing and reheating The temperatures specified in the oxidation treatment, annealing, and cooling after annealing described below are all "steel sheet temperatures", more specifically, the surface temperatures of the steel sheet. A non-oxidizing atmosphere described below refers to an atmosphere in which iron does not oxidize, and is an atmosphere in which selective oxidation of easily oxidizable additive elements such as Si and Mn is permitted. A reducing atmosphere refers to an atmosphere in which iron oxide can be reduced to iron.
[0026] The type of hot-dip galvanized steel sheet to which the present invention is applied is not particularly limited as long as it is a plated steel sheet having a plating layer mainly composed of zinc, and includes not only hot-dip galvanized steel sheet (GI), but also steel sheet subjected to alloying treatment after hot-dip galvanizing (GA). The types of hot-dip galvanized steel sheet include hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA), as well as hot-dip galvanized steel sheet (GI) and galvannealed steel sheet (GA), hot-dip zinc-aluminum alloy plated steel sheet, hot-dip zinc-aluminum-silicon alloy plated steel sheet, hot-dip zinc-aluminum-magnesium alloy plated steel sheet, and the like, and the detailed plating composition of each is not limited.
[0027] In the following description, the units of "%" for the content of each element in the composition of the steel sheet (also referred to as the base steel sheet or base steel sheet), the content of each element in the composition of the plating bath, and the degree of alloying of the plating layer are all "mass%", and the units of "%" for the hydrogen concentration in the atmosphere during annealing and cooling are all "volume%". Furthermore, "high strength" steel sheet means that the tensile strength TS of the steel sheet measured in accordance with JIS Z2241 (2011) is 780 MPa or more.
[0028] The manufacturing method of the present invention is a manufacturing method of a hot-dip galvanized steel sheet, in which a base steel sheet having a predetermined steel composition and distribution form of inclusions is annealed in a non-oxidizing atmosphere, and then the base steel sheet is hot-dip galvanized, and the annealing has a first annealing step and a second annealing step. The annealing can be performed in a non-oxidizing atmosphere. In the first annealing step, the steel sheet is annealed in a reducing atmosphere with a high hydrogen concentration and a predetermined dew point, thereby reducing natural iron oxide present in the surface layer of the steel sheet. In the subsequent second annealing step, the steel sheet is annealed in a non-oxidizing atmosphere with a low hydrogen concentration and a predetermined dew point, and hydrogen dissolved in the steel is released from the steel sheet. The annealed steel sheet is cooled to a predetermined temperature, and then immersed in a hot-dip galvanized bath to be subjected to hot-dip galvanized plating. The manufacturing method of the present invention includes a case where alloying treatment is performed after hot-dip galvanized plating to produce a galvannealed hot-dip galvanized plated steel sheet. The hot-dip galvanized plated steel sheet (including the galvannealed hot-dip galvanized plated steel sheet) thus obtained has a hydrogen amount (hydrogen concentration H L The hydrogen concentration H H The total amount of these elements is controlled to 0.20 ppm by mass or less, resulting in a beautiful surface appearance and good resistance to delayed fracture.
[0029] Furthermore, by performing an oxidation treatment in which iron oxide is generated on the surface layer of the steel sheet in a specified oxidizing atmosphere before annealing, it is possible to obtain an even more beautiful surface appearance. Also, by optimizing the atmosphere in which the steel sheet after annealing is cooled, or by reheating the steel sheet after plating in an atmosphere having a specified hydrogen concentration, it is possible to improve the delayed fracture resistance to an even higher level. The structure and chemical composition of the steel sheet (base steel sheet) that serves as the base material of the hot-dip galvanized steel sheet will be described in detail later. In the present invention, the oxidation treatment and the subsequent annealing in a non-oxidizing atmosphere are usually performed in a continuous annealing furnace having, in order from the inlet side, an oxidation zone (zone for the oxidation treatment), a reduction zone (zone for the first annealing step of annealing), a soaking zone (zone for the second annealing step of annealing), and a cooling zone. Here, the oxidation treatment is not an essential step and can be carried out appropriately as necessary.
[0030] The manufacturing method of the present invention will be described below in the order of oxidation treatment, annealing (first annealing step, second annealing step), cooling after annealing (first cooling step, second cooling step), hot-dip galvanizing, and reheating.
[0031] Oxidation treatment process In the oxidation treatment, the steel sheet temperature is controlled to 400°C or more and 900°C or less in an atmosphere containing 1000 volume ppm or more of O2, thereby forming iron oxide on the surface layer of the steel sheet (base steel sheet). The atmosphere for the oxidation treatment may contain one or more of N2, CO, CO2, H2O, and NOx in addition to O2. N2 can be contained as an inert gas, CO as a gas for adjusting oxidation and reduction, CO2 as an inert gas, and H2O as a gas for adjusting oxidation and reduction. CO, CO2, H2O, and NOx can also be contained as fuel gas, gas derived from the components of the steel sheet to be annealed, impurity gas in the air, or fuel combustion gas.
[0032] In the present invention, the steel sheet is oxidized by this oxidation treatment, and then reduced in the subsequent annealing (first annealing step) to form a reduced iron layer on the surface layer of the steel sheet, thereby preventing Si and Mn from diffusing into the surface layer of the steel sheet and oxidizing, thereby further improving the galvanizability. In the present invention, in which a low hydrogen atmosphere is used in the second annealing step, the oxidation treatment in an atmosphere containing 1000 volume ppm or more of O2 highly improves and simultaneously achieves both excellent surface quality and excellent delayed fracture resistance. Furthermore, the improvement effect is particularly remarkable in steel containing 0.1% or more of Si and 1.5% or more of Mn. The oxidation of steel sheet is promoted by setting the O2 concentration in the atmosphere in which the oxidation treatment is performed to 1000 ppm by volume or more. If the O2 concentration is less than 1000 ppm by volume, the oxidation of the steel sheet is insufficient, and oxides of Si and Mn are formed, which may result in a decrease in galvanic properties. The upper limit of the O2 concentration is not particularly limited, but in order to avoid problems such as pick-up onto the transport roll due to peroxidation, it is preferably 50,000 ppm by volume or less, and more preferably 10,000 ppm by volume or less. The atmosphere for the oxidation treatment may contain N2, CO, CO2, H2O, NOx, etc. depending on the gas used, and the ratio of these gases is not particularly limited. In addition, although a more beautiful surface appearance can be obtained by the oxidation treatment, this step is not an essential requirement because it is possible to obtain a hot-dip galvanized steel sheet with excellent delayed fracture resistance without the oxidation treatment.
[0033] In the oxidation treatment, the oxidation of the steel sheet is promoted by setting the steel sheet temperature to 400° C. or higher. If the steel sheet temperature is less than 400° C., the amount of oxidation becomes insufficient, and oxides of Si and Mn are formed, which may reduce the effect of improving the plateability. On the other hand, if the steel sheet temperature exceeds 900°C, the amount of oxidation of the steel sheet becomes excessive, and reduction is not completed in the subsequent reduction annealing (first annealing step), and the remaining iron oxide may impair the galvanizing property. For this reason, the oxidation treatment is preferably performed at 400°C or more and 900°C or less. Here, performing the oxidation treatment at 400°C or more and 900°C or less means that the oxidation treatment temperature is at least in the range of 400 to 900°C and does not exceed 900°C. That is, in the present invention, as long as the oxidation treatment is performed at a temperature of 400°C or more and 900°C or less in an atmosphere containing 1000 volume ppm or more of O2, the oxidation treatment may also be performed at a temperature below 400°C (for example, when the oxidation treatment is performed during the temperature rise process from 300°C to 700°C). The oxidation treatment is preferably carried out for a treatment time in the range of 1 to 30 seconds. That is, from the viewpoint of securing a sufficient amount of oxidation and improving plating properties, the treatment time is preferably 1 second or more, more preferably 2 seconds or more, and even more preferably 3 seconds or more. On the other hand, from the viewpoint of preventing excessive oxidation and suppressing pick-up, the treatment time is preferably 30 seconds or less, more preferably 20 seconds or less, and even more preferably 15 seconds or less.
[0034] The oxidation treatment process may include a process of heating the steel sheet (base steel sheet) to a temperature for annealing. For example, a soaking chamber capable of controlling the atmosphere is provided during the process of heating the steel sheet, and the steel sheet surface can be oxidized by maintaining a constant temperature in a predetermined atmosphere. It is also possible to oxidize the steel sheet surface by controlling the atmosphere in the furnace while heating the steel sheet in a direct-fire heating furnace equipped with a direct-fire burner. By simultaneously performing the temperature increase and oxidation treatment, the furnace can be made compact and the production rate can be improved, which is an industrial advantage. When the surface of the steel sheet is oxidized while the temperature of the steel sheet is increased, a sufficient amount of oxidation can be obtained by providing an oxidizing atmosphere over a temperature increase range (temperature increase range) of 50°C or more after the steel sheet temperature reaches 400°C. When the surface of the steel sheet is oxidized while the temperature of the steel sheet is increased, the temperature increase rate in the temperature range for oxidation is preferably 3 to 25°C / s from the viewpoint of ensuring an appropriate amount of oxidation.
[0035] Here, the direct flame burner for the oxidation treatment can be a burner that heats the steel plate by directly applying the burner flame, which is a mixture of fuel such as coke oven gas (COG), a by-product gas from steel mills, and air, to the surface of the steel plate. Heating with such a direct flame burner has the advantage that the length of the heating furnace can be shortened and the conveying speed of the steel plate can be increased because the temperature of the steel plate is increased faster than by a radiation heating method. Furthermore, if the air ratio of the direct flame burner is set to 0.95 or more and the ratio of air to fuel is increased, unburned oxygen remains in the flame, and the oxygen can promote the oxidation of the steel plate. Therefore, by adjusting the air ratio, it is possible to control the oxygen concentration in the atmosphere. In addition to COG, liquefied natural gas (LNG), ammonia gas, hydrogen gas, etc. can be used as fuel for the direct flame burner.
[0036] Annealing First annealing process In the first annealing step (first annealing step), the steel sheet is held at a temperature of 650°C to 950°C for 20 s to 150 s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 8.0% to 25%, in which iron oxide is reduced. In the first annealing step, natural iron oxide present on the surface layer of the steel sheet is reduced in a reducing atmosphere to ensure galvanizability. Since the reduction hardly progresses in the subsequent second annealing step in a low hydrogen concentration atmosphere, it is preferable to complete the reduction of iron oxide in this first annealing step. This first annealing step is an essential step for obtaining a good plating appearance. Furthermore, when oxidation treatment is performed, the intentionally formed iron oxide is reduced in a reducing atmosphere in the first annealing step of this reduction annealing to form a reduced iron layer on the steel sheet surface layer, thereby preventing Si and Mn from diffusing into the steel sheet surface layer and being oxidized, and making the appearance even more beautiful. Similarly, even when oxidation treatment is performed, reduction hardly progresses in the subsequent second annealing step in a low hydrogen concentration atmosphere, so it is preferable to reduce the iron oxide in this first annealing step.
[0037] If the annealing temperature of the steel sheet in the first annealing step is less than 650°C, reduction will be insufficient, and iron oxide will become roll pick-up, causing defects in the steel sheet. In addition, in the subsequent second annealing step, the iron oxide will not be substantially reduced, causing bare spots. On the other hand, if the annealing temperature of the steel sheet exceeds 950°C, the life of the furnace body is significantly reduced. For this reason, the annealing temperature of the steel sheet is set to 650°C or higher and 950°C or lower. When the base steel sheet (base steel sheet) is a cold-rolled steel sheet, the annealing temperature is preferably set to 750°C or higher from the viewpoint of ensuring the required strength and ductility by recrystallization. In order to obtain a high-strength steel sheet having a tensile strength of 780 MPa or more, it is necessary to ensure a predetermined total area ratio of martensite, bainite and retained γ (retained austenite), and the annealing temperature is preferably 780° C. or more. Increasing the annealing temperature in the first annealing step promotes selective oxidation of Si and Mn and increases the amount of hydrogen in the steel. In the present invention, by controlling the atmosphere and holding time in the first annealing step and the second annealing step, the effects of promoting selective oxidation and increasing the amount of hydrogen in the steel can be reduced, and therefore excellent surface quality and excellent resistance to delayed fracture can be provided. To lower the dew point of the atmosphere in the first annealing process below -55°C requires special equipment, which increases costs, but at +30°C or less, the iron oxide in the steel sheet surface layer can be reduced, and the selective oxidation of Si and Mn can be suppressed within the specified annealing time range. If the dew point exceeds +30°C, the dew point distribution in the furnace becomes large, making dew point control difficult and raising concerns about the impact on the furnace body. For this reason, the dew point is set to be between -55°C and +30°C. The dew point is preferably -50°C or higher, and more preferably -45°C or higher. The dew point is preferably 20° C. or lower, and more preferably 15° C. or lower.
[0038] In the first annealing step, the higher the hydrogen concentration, the faster the reduction of iron oxide is completed and the selective oxidation of Si and Mn is suppressed, but the higher the hydrogen concentration, the easier it is for hydrogen to dissolve in the steel, and the delayed fracture resistance property decreases. In this regard, if the hydrogen concentration is less than 8.0%, the reduction is insufficient. On the other hand, if the hydrogen concentration exceeds 25%, the effect of the reduction is saturated and a large amount of hydrogen is dissolved in the steel, making it difficult to sufficiently reduce the amount of hydrogen in the steel in the subsequent second annealing step. For this reason, the hydrogen concentration in the first annealing step is set to 8.0% or more and 25% or less. In addition, when an oxidation treatment is performed, the hydrogen concentration is preferably 10% or more in order to perform sufficient reduction. On the other hand, from the viewpoint of production cost and reduction of hydrogen in the steel, the hydrogen concentration is preferably 22% or less, and more preferably 18% or less.
[0039] If the holding time in the first annealing step is less than 20 seconds at 650°C or more and 950°C or less, the reduction is not fully completed. On the other hand, if the holding time exceeds 150 seconds, the area ratio of martensite and bainite required to obtain high-strength steel with a tensile strength of 780 MPa or more cannot be sufficiently secured. In addition, since the reduction is fully completed with a holding time of 150 seconds or less, if the holding time exceeds 150 seconds, the productivity is unnecessarily reduced. In addition, selective oxidation of Si and Mn progresses, deteriorating the surface quality and plating adhesion. The amount of hydrogen in the steel is saturated with a holding time of about 20 seconds, and the effect of the holding time is not large. For this reason, the holding time in the first annealing step at 650°C or more and 950°C or less is set to 20 seconds or more and 150 seconds or less. The retention time is preferably 30 seconds or more, and more preferably 40 seconds or more. The retention time is preferably 130 seconds or less, and more preferably 90 seconds or less.
[0040] Second annealing process In the second annealing step, the steel sheet (base steel sheet) that has been through the first annealing step is held at a temperature of 700°C to 950°C for 30 seconds to 300 seconds in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2% to less than 8.0%. In this second annealing step, the steel sheet that has been reduced in the first annealing step is maintained in a low hydrogen atmosphere, thereby releasing hydrogen from the steel sheet. If the annealing temperature (holding temperature, soaking temperature) of the steel sheet in the second annealing step is less than 700°C, dehydrogenation is not promoted. On the other hand, if the annealing temperature exceeds 950°C, the furnace body is significantly affected. For this reason, the annealing temperature of the steel sheet is set to 700°C or higher and 950°C or lower. From the viewpoint of reducing the amount of hydrogen in the steel, the annealing temperature in the second annealing step is preferably set to 860°C or lower, and more preferably to 830°C or lower. In order to obtain a high-strength steel sheet having a tensile strength of 780 MPa or higher, it is necessary to ensure a predetermined total area ratio of martensite, bainite, and residual γ, and therefore the annealing temperature in the second annealing step is preferably set to 780°C or higher.
[0041] In the second annealing process, the lower the dew point, the smaller the impact on the furnace body, but to make the dew point less than -50°C, special equipment is required to control the dew point, which increases costs. On the other hand, if the dew point exceeds +30°C, the reduced Fe formed in the first annealing process may be reoxidized and impair the plating properties, and it is also difficult to control the dew point, which raises concerns about the impact on the furnace body. For this reason, the dew point is set to be between -50°C and +30°C. From the viewpoint of controllability, the dew point is preferably +20°C or less, and more preferably +15°C or less. The dew point is preferably -45°C or higher, and more preferably -40°C or higher. In the second annealing step, the lower the hydrogen concentration, the more hydrogen dissolved in the steel sheet in the first annealing step is released. However, it is difficult to uniformly control the hydrogen concentration in the furnace to less than 0.2%, and there is a concern that the steel sheet may be reoxidized in the areas with low hydrogen concentration, so the hydrogen concentration is set to 0.2% or more. On the other hand, if the hydrogen concentration is 8.0% or more, the amount of hydrogen released at 150°C or more and 350°C or less, particularly when measured by temperature rise analysis, cannot be sufficiently reduced, so the hydrogen concentration is set to less than 8.0%. From the above viewpoints, the hydrogen concentration is preferably 1.0% or more, and more preferably 2.0% or more. Similarly, the hydrogen concentration is more preferably less than 5.0%.
[0042] If the holding time in the second annealing step at 700°C to 950°C is less than 30s, hydrogen release is not fully completed. On the other hand, hydrogen release is fully completed with a holding time of 300s or less, so if the holding time exceeds 300s, productivity is reduced. In addition, selective oxidation of Si and Mn progresses, deteriorating surface quality and plating adhesion. For this reason, the holding time in the second annealing step at 700°C to 950°C is set to 30s to 300s. In particular, from the viewpoint of sufficiently releasing hydrogen that is released at 150°C or higher and 350°C or lower when measured by temperature rise analysis, it is preferable that the holding time at 700°C or higher and 950°C or lower in the second annealing step be 40 s or longer. The retention time is preferably 250 seconds or less, and more preferably 200 seconds or less. In the present invention, a high concentration of hydrogen is required to reduce the iron oxide naturally present on the steel sheet surface or the iron oxide produced by oxidation treatment in the first annealing step of annealing. Since a large amount of hydrogen is dissolved in the steel accordingly, the balance between reduction and dehydrogenation is important, and therefore it is necessary to optimize the conditions for the first annealing step and the second annealing step in the annealing step as described above.
[0043] Although the method for changing the hydrogen concentration in the first annealing step and the second annealing step is not particularly specified, it is possible to easily control the atmospheres in the first annealing step and the second annealing step individually by dividing the furnace into two furnaces, using furnaces connected via seal rolls, and controlling the hydrogen concentration and dew point of the gas fed into each furnace. In the present invention, it is preferable to anneal the steel sheet using a continuous annealing furnace capable of controlling two or more separate different atmospheres.
[0044] ·Cooling process The base steel sheet that has been annealed (second annealing step) is cooled from the holding temperature of 700°C or more and 950°C or less in the second annealing step (final holding temperature in the second annealing step) to a temperature of 150°C or more and 550°C or less. Thereafter, after heating as necessary, the steel sheet is immersed in a hot-dip galvanized plating bath to perform hot-dip galvanized plating. Here, the final holding temperature in the second annealing step refers to the temperature at which the steel sheet that has been annealed within ranges that satisfy the requirements of the annealing temperature, hydrogen concentration, dew point, and holding time in the above-mentioned second annealing step falls outside at least one of the above requirements. In this cooling process, in an atmosphere with a dew point of -20°C or lower and a hydrogen concentration of 0.2% or more and 25% or less, the average cooling rate is from a holding temperature of 700°C or more and 950°C or less in the second annealing process (the final holding temperature in the second annealing process) to a temperature of 150°C or more and 550°C or less, and is 3°C / s or more and 300°C / s or less. Here, the above average cooling rate can be obtained by dividing the difference between the cooling start temperature (final holding temperature of the second annealing step) (°C) and the cooling end temperature (150°C or higher and 550°C or lower) by the cooling time (s). In the cooling step, from the holding temperature of 700°C or more and 950°C or less in the second annealing step (final holding temperature in the second annealing step) to 550°C, it is preferable to set the atmosphere to a dew point of -20°C or less and a hydrogen concentration of 0.2% or more and 25% or less, and the average cooling rate in this temperature range to 3°C / s or more and 30°C / s or less. Also, in the temperature range of 550°C or less and 150°C or more, it is preferable to set the atmosphere to a dew point of -20°C or less and a hydrogen concentration of 0.2% or more and 25% or less, and the average cooling rate to 5°C / s or more. Moreover, it is preferable that the average cooling rate in this case is 300°C / s or less. Moreover, when heating is performed after cooling, the heating rate is preferably 5°C / s or more. This cooling step can also be performed in two separate cooling zones with different atmospheres as described below, and will be described below as a first cooling step and a second cooling step. Here, the above average cooling rate can be obtained by dividing the difference between the cooling start temperature (final holding temperature of the second annealing step) (°C) and the temperature up to 550°C, and between 550°C and the cooling end temperature (150°C or more and 550°C or less), by the respective cooling times (s). In addition, the dew point in the cooling process refers to a dew point of -20°C or less from the start to the end of cooling. The hydrogen concentration in the cooling step means that the hydrogen concentration is 0.2% or more and 25% or less from the start to the end of cooling. The lower limit of the dew point in the cooling step is not particularly limited, but in order to lower the dew point below -55°C, special equipment is required to lower the dew point, which increases costs. Therefore, it is preferable that the dew point in the cooling step is -55°C or higher.
[0045] ·First cooling process The cooling process includes a first cooling process, in which the base steel sheet on which the annealing (second annealing process) has been completed is cooled in an atmosphere with a dew point of -20°C or lower and a hydrogen concentration of 0.2 vol% or higher and less than 8.0 vol% over a period of 10 s or more at an average cooling rate of 3°C / s or higher and 25°C / s or lower in the temperature range from the holding temperature of the second annealing process of 700°C or higher and 950°C or lower (final holding temperature of the second annealing process) to a steel sheet temperature of 650°C or lower. By cooling at an average cooling rate of 3°C / s or more in the temperature range from the final holding temperature in the second annealing step to a steel sheet temperature of 650°C or less, the desired steel sheet strength can be obtained. The steel sheet temperature is preferably 600° C. or higher. If the steel sheet temperature is less than 600° C., the hydrogen reduction effect is saturated and it becomes difficult to increase the cooling rate, which may make it difficult to ensure the desired microstructure and strength. If the average cooling rate is less than 3°C / s, the strength of the steel sheet is likely to decrease. Therefore, the average cooling rate is set to 3°C / s or more. The average cooling rate is preferably 5°C / s or more. On the other hand, if the average cooling rate exceeds 25°C / s in the temperature range up to the steel sheet temperature of 650°C or less, the retention time in the atmosphere with a hydrogen concentration of 0.2% or more and less than 8.0% in the first cooling step becomes short, and it becomes impossible to release the relatively stable semi-diffusible hydrogen that was not released in the first annealing step. Therefore, the average cooling rate is set to 25°C / s or less. The average cooling rate is preferably 23°C / s or less, and more preferably 20°C / s or less. Furthermore, when the hydrogen content in the atmosphere is 8.0% or more, hydrogen released at temperatures between 150° C. and 350° C. when measured by temperature ramp analysis is likely to remain in the steel sheet. Here, the final holding temperature in the second annealing step refers to the temperature at which the steel sheet annealed within ranges satisfying the requirements of the annealing temperature, hydrogen concentration, dew point, and holding time in the second annealing step falls outside at least one of the requirements. The average cooling rate (°C / s) is obtained by dividing the difference between the cooling start temperature (final holding temperature in the second annealing step) (°C) and the cooling end temperature (steel sheet temperature of 650°C or less) by the cooling time (s). The cooling end temperature (steel sheet temperature of 650°C or less) refers to the temperature at which the hydrogen concentration transitions from less than 8.0% to 8.0% or more.
[0046] The atmosphere of the cooling zone will be described. Hydrogen has a high cooling ability, so the higher the hydrogen concentration in the atmosphere, the higher the cooling rate can be. However, if the hydrogen concentration is too high, hydrogen may penetrate into the steel sheet during cooling, and the release of hydrogen, particularly at 150°C to 350°C, when measured by temperature rise analysis, is insufficient. When cooling from a relatively high temperature, the cooling efficiency is high, so in the region of 650°C or higher, the amount of hydrogen required to obtain a cooling rate of 3°C / s or more is less than that required for cooling at a low temperature. In addition, the cooling rate required to obtain the required strength is smaller in the region of 650°C or higher than the cooling rate below 650°C, which has the greatest effect on the strength of the steel sheet. In addition, by providing a cooling section in which the hydrogen concentration is less than 8.0% in the temperature range below the holding temperature of the second annealing temperature, the hydrogen released at 150°C to 350°C described above can be further reduced. Therefore, in the first cooling step, a section in which the hydrogen concentration is 0.2% to less than 8.0% is provided within the temperature range from the final holding temperature of the second annealing step to the steel sheet temperature of 650°C or lower. If the hydrogen concentration is less than 0.2%, there is a risk that a sufficient cooling rate cannot be ensured, and the strength of the steel sheet is likely to decrease. On the other hand, if the hydrogen concentration is 8.0% or more, the cooling rate will be faster, but hydrogen may penetrate into the steel sheet during cooling, and hydrogen that is not fully released in the first annealing step and is released at temperatures between 150°C and 350°C when measured by temperature rise analysis will not be fully released. Therefore, the hydrogen concentration is set to 0.2% or more and less than 8.0%. The hydrogen concentration is preferably 0.5% or more, and more preferably 1.0% or more. In addition, the hydrogen concentration is preferably 4.0% or less, and more preferably 3.0% or less.
[0047] Furthermore, by setting the dew point to -20°C or lower in the section where the atmosphere has a hydrogen concentration of 0.2% or higher and lower than 8.0%, it is possible to suppress the reoxidation of the steel sheet at low temperatures and the deterioration of platability. In other words, if the dew point exceeds -20°C, the steel sheet is likely to reoxidize at low temperatures and the platability is likely to deteriorate. It is preferable to retain the steel sheet for 10 seconds or more in the section where the atmosphere has a dew point of -20°C or lower and a hydrogen concentration of 0.2% or higher and lower than 8.0%. By retaining the steel sheet for 10 seconds or more, it is possible to promote the release of hydrogen in the steel, and further reduce the hydrogen released at the above-mentioned temperature of 150°C or higher and 350°C or lower. Although there is no particular lower limit, a temperature lower than -55°C requires special equipment for lowering the dew point, which increases costs. Therefore, the dew point in the first cooling step is preferably -55°C or higher.
[0048] The section in which the dew point is -20°C or less and the hydrogen concentration is 0.2% or more and less than 8.0% may be a section in which continuous cooling is performed or a section in which cooling is stopped and the atmosphere is maintained at a substantially constant temperature. The above-mentioned section in which the dew point is -20°C or less and the hydrogen concentration is 0.2% or more and less than 8.0% may be provided in a temperature range of at least the holding temperature of the second annealing temperature to 650°C or less. For example, it may be in a range of from the holding temperature of the second annealing temperature to 650°C, or may be in a range of from the holding temperature of the second annealing temperature to 620°C. As described later, in order to set the cooling start temperature of the second cooling step to 600°C, the above-mentioned section in which the dew point is -20°C or less and the hydrogen concentration is 0.2% or more and less than 8.0% is preferably set to a temperature above 600°C.
[0049] ·Second cooling process The steel sheet (base steel sheet) that has completed the first cooling step is cooled from the cooling start temperature (600°C) to a steel sheet temperature of 150°C to 550°C at an average cooling rate of 10°C / s or more in an atmosphere with a dew point of -20°C or less and a hydrogen concentration of 8.0% to 25%. Thereafter, after heating as necessary, the steel sheet is immersed in a hot-dip galvanized bath to perform hot-dip galvanized plating. By cooling at an average cooling rate of 10°C / s or more in the temperature range from 600°C to a steel sheet temperature of 150°C or more and 550°C or less, the desired steel sheet strength can be obtained and hydrogen in the atmosphere can be prevented from penetrating into the steel sheet during cooling. In the range of 600°C or less, the cooling rate has a large effect on the strength of the steel sheet, so if the average cooling rate is less than 10°C / s, the strength of the steel sheet is likely to decrease and hydrogen in the atmosphere is likely to penetrate into the steel sheet, resulting in a decrease in delayed fracture resistance. Therefore, the average cooling rate is set to 10°C / s or more. The average cooling rate is preferably 13°C / s or more. The above average cooling rate (°C / s) is obtained by dividing the difference between 600°C and the steel sheet temperature in the range of 150°C to 550°C by the cooling time (s). In addition, the temperature range of more than 600°C and less than 650°C is a transition zone for switching the hydrogen concentration, and the steel plate may be cooled at a cooling rate of 3°C / s or more and 25°C / s or less with a dew point of -20°C or less and a hydrogen concentration of 0.2% or more and 25% or less.
[0050] In the second cooling process, the cooling temperature is lower than that in the first cooling process, so even if a higher concentration of hydrogen is present in the atmosphere than in the first cooling process, hydrogen is less likely to penetrate into the steel sheet and is less likely to become relatively stable quasi-diffusible hydrogen. On the other hand, the second cooling process, which is in a low temperature range, has a greater impact on strength reduction when the cooling rate is reduced than in the first cooling process. Therefore, the hydrogen concentration in the cooling zone atmosphere is set to 8.0% or more and 25% or less. If the hydrogen concentration is less than 8.0%, there is a risk that a sufficient cooling rate cannot be ensured, and the strength of the steel sheet is likely to decrease. On the other hand, if the hydrogen concentration exceeds 25%, the cooling effect is saturated and hydrogen is likely to penetrate into the steel sheet during cooling, and the amount of hydrogen released at 150°C to 350°C when measured by heating analysis also increases, making the delayed fracture resistance property more likely to decrease. The hydrogen concentration is preferably 10% or more, and more preferably 12% or more. Moreover, the hydrogen concentration is preferably 20% or less, and more preferably 15% or less. Furthermore, by setting the dew point to -20°C or lower, it is possible to suppress the reoxidation of the steel sheet at low temperatures, which would otherwise cause a decrease in galvanizability. That is, if the dew point exceeds -20°C, the steel sheet is likely to be reoxidized at low temperatures, which would cause a decrease in galvanizability. Although there is no particular lower limit, a temperature lower than -55°C requires special equipment for lowering the dew point, which increases costs. Therefore, the dew point in the second cooling step is preferably -55°C or higher.
[0051] After the second cooling step, the base steel sheet is cooled to 150°C or more and 550°C or less, and then, before being immersed in the coating bath, the steel sheet can be held for 5s or more at a temperature range of 150°C or more and 550°C or less, with a dew point of 0°C or less and a hydrogen concentration of 15% or less. By holding the steel sheet at 150°C or more and 550°C or less after the second cooling step, it is possible to partially generate bainite and martensite, and such a treatment can increase the amount of residual γ generated in the final product and the C concentration in the residual γ. As a result, it is possible to improve ductility, stretch flange formability, and bendability. It is also possible to generate bainitic ferrite and blocky martensite to reduce YR and improve ductility. From the viewpoint of obtaining such effects, the holding time is preferably 5s or more, more preferably 10s or more, and even more preferably 20s or more. During holding at 150°C or higher and 550°C or lower, a large amount of untransformed austenite remains in the steel, so the amount of hydrogen released from the steel is not large, but it is possible to slightly reduce the amount of hydrogen in the steel by setting the hydrogen concentration in the atmosphere to 15% or lower. From the viewpoint of reducing hydrogen in the steel, a holding time of 20 s or longer is preferable. On the other hand, from the viewpoint of minimizing the decrease in the strength of the steel sheet, a holding time of 120 s or shorter is preferable, and 100 s or shorter is more preferable.
[0052] Hot-dip galvanizing process The conditions of the hot dip galvanizing treatment are not particularly limited, and may be general conditions. That is, preferably under the above-mentioned conditions, the base steel sheet is cooled to a temperature of 150°C or more and 550°C or less in the cooling step, and then heated to about the plating bath temperature as necessary, and immersed in the hot dip galvanizing bath to be plated. In the case of GA or GI, the plating bath is composed of Zn, Al, and unavoidable impurities, and the components are not particularly specified, but the Al concentration in the bath is preferably 0.05% or more and 0.250% or less. If the Al concentration in the bath is less than 0.05%, the occurrence of bottom dross increases, and the dross easily adheres to the steel sheet and becomes a defect. On the other hand, if it exceeds 0.190%, the top dross increases, and the dross also easily adheres to the steel sheet and becomes a defect, and the addition of Al leads to an increase in cost. In addition, the hot dip galvanizing bath temperature is preferably 440 to 500°C.
[0053] · Alloying process In addition, after the above-mentioned hot-dip galvanizing treatment in the hot-dip galvanizing step, the alloying treatment can be performed subsequently, and the conditions of the alloying treatment when the alloying treatment is performed are not particularly limited. As the conditions of the alloying treatment, it is preferable to perform the alloying treatment by heating the steel sheet having the zinc-based plating layer (hot-dip galvanized steel sheet) to an alloying temperature of 430 ° C or more after the above-mentioned hot-dip galvanizing treatment. The above-mentioned alloying temperature is preferably 600 ° C or less. If the alloying temperature is less than 430 ° C, the Fe-Zn alloying speed is slow, and alloying may be difficult. On the other hand, if the alloying temperature exceeds 600 ° C, Fe-Zn alloying becomes excessive, and in addition to the deterioration of the plating appearance and plating adhesion, untransformed austenite may transform into pearlite, making it impossible to obtain the desired tensile strength. The alloying temperature is more preferably 450 ° C or more. The alloying temperature is more preferably 570 ° C or less.
[0054] Reheating process Next, the steel sheet that has been subjected to the treatment in the hot dip galvanizing process or further to the treatment in the alloying process may be cooled to room temperature to 450°C as required, and further subjected to temper rolling and heat treatment as required, and then may be held in a temperature range of 200°C to 450°C for a reheating time of 5 s to 600 s in an atmosphere with a hydrogen concentration of 15 vol% or less, and then cooled. The cooling may be performed to room temperature. From the viewpoint of promoting the release of hydrogen that is released at 150°C to 350°C when measured by temperature rise analysis in steel during reheating, it is advantageous to lower the hydrogen concentration in the atmosphere. Therefore, the hydrogen concentration is preferably 15% or less, and more preferably 5% or less. The lower limit of the hydrogen concentration is not particularly limited. However, hydrogen is unavoidably contained in the atmosphere. Therefore, the hydrogen concentration may be, for example, 0.00001% by volume or more. The remaining gas other than hydrogen (H2) in the atmosphere during reheating is not particularly limited. As an example, the remaining gas may be N2, O2, H2O, CO 2、 Ar and unavoidable impurities, and combinations thereof. The ratio of these is not particularly limited. This reheating may be performed in the air. In order to obtain a sufficient effect of reducing hydrogen in steel that is released at 150° C. or higher and 350° C. or lower when measured by temperature rise analysis, the reheating temperature is preferably 200° C. or higher. On the other hand, if the reheating temperature exceeds 450°C, the plating layer may remelt, resulting in deterioration of the appearance. Therefore, the reheating temperature is preferably 200°C or higher and 450°C or lower. The reheating temperature is more preferably 250°C or higher. The reheating temperature is more preferably 400°C or lower. Here, the reheating temperature is the maximum temperature reached during reheating. In addition, the temperature may be constant or may vary as long as it is within the range of 200°C or higher and 450°C or lower. If the reheating time is less than 5 seconds, the effect of reducing hydrogen released at 150°C to 350°C as measured by temperature rise analysis in steel may not be sufficiently obtained. Therefore, the reheating time is preferably 5 seconds or more. The reheating time is more preferably 10 seconds or more, and further preferably 30 seconds or more. On the other hand, from the viewpoint of productivity, the reheating time is preferably 600 seconds or less. The reheating time is a holding time in a temperature range of 200°C to 450°C, which is equal to or higher than the cooling stop temperature after the hot dip galvanizing treatment or further after the alloying treatment.
[0055] The above-mentioned temper rolling may be carried out before and / or after the reheating treatment. When temper rolling is carried out, it may be carried out either before or after the reheating treatment, or both, but it is preferable that the elongation rate is 0.05% or more and 1.0% or less. Note that, before or after the above-mentioned reheat treatment step, a step of holding the steel sheet in an atmosphere with a hydrogen concentration of 15% or less at a temperature of room temperature to less than 200° C. When holding the steel sheet in an atmosphere with a hydrogen concentration of 15% or less at a temperature of room temperature to less than 200° C., holding the steel sheet at a temperature of 10 to 25° C. for 4 days or more, at a temperature higher than 25° C. and lower than 80° C. for 1 day or more, or at a temperature higher than 80° C. and lower than 200° C. for 30 minutes or more reduces hydrogen released from the steel at a temperature between 25° C. and 140° C. to 0.2 ppm or less when measured by temperature rise analysis.
[0056] The conditions other than those mentioned above are not particularly limited, and may be those according to conventional methods.
[0057] <Hot-dip galvanized steel sheet> Next, the high-strength hot-dip galvanized steel sheet will be described. The hot-dip galvanized steel sheet of the present invention contains, by mass%, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and 3.00% or less, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (not including 0%), S: 0.0030% or less (not including 0%), sol.Al: 0.1% or less (not including 0%), N: 0.0070% or less (not including 0%), and O: 0.0030% or less (not including 0%), or further contains one or more groups selected from the following groups A, B, C, and D, Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the above, Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following, Group C Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more of the following: Group D Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following: H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following: A base steel sheet having a composition with the balance being Fe and unavoidable impurities; A zinc-based plating layer is formed on the surface of the base steel sheet, Furthermore, the inclusions contained in the base steel sheet satisfy the following conditions (i) and (ii), and the number of inclusions is 10 / mm 2 The amount of hydrogen released from the base steel sheet at a temperature between room temperature and 350°C (hydrogen concentration H L ) is 0.30 mass ppm or less, and the amount of hydrogen released at 150 to 350 ° C (hydrogen concentration H H ) is 0.20 mass ppm or less, the number of uncoated defects is less than 3 within an area of 1 m x 1 m on the steel sheet surface, and the tensile strength is 780 MPa or more. (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When an inclusion group is composed of two or more of the above-mentioned inclusion particles, the major axis length of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less.
[0058] There is no particular restriction on the coating weight of the zinc-based coating layer on the base steel sheet by hot-dip galvanizing treatment, but it is generally set to 20 to 120 g / m 2 It may be. The coating weight of the zinc-based coating layer on one side is 20g / m 2 If the thickness is less than 120g / m2, not only is the corrosion resistance likely to decrease, but it is also difficult to control the coating weight. 2 There are no particular restrictions on the method for adjusting the coating weight, but gas wiping is generally used, and adjustments are made by the gas pressure, the distance between the wiping nozzle and the steel sheet, etc. When alloying treatment is performed after hot dip galvanizing treatment, the degree of alloying of the galvanized layer after alloying treatment is not particularly limited, but the degree of alloying is preferably 7 to 15%. If the degree of alloying is less than 7%, the η phase remains and press formability is likely to decrease, while if it exceeds 15%, plating adhesion is likely to decrease.
[0059] The base steel sheet (base steel sheet) may be either a cold-rolled steel sheet or a hot-rolled steel sheet. Since delayed fracture resistance is a problematic property in high-strength steel sheets, the steel sheet is preferably a high-strength steel sheet having a tensile strength TS of 780 MPa or more, preferably 980 MPa or more, more preferably 1180 MPa or more, even more preferably 1310 MPa or more, and even more preferably 1470 MPa or more.
[0060] In the present invention, the inclusion group contained in the base steel sheet (base steel sheet) satisfies the following conditions (i) and (ii), and the inclusion group is 10 pieces / mm 2 The following is the result. (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When an inclusion group is composed of two or more of the above-mentioned inclusion particles, the major axis length of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less.
[0061] Steel contains inclusions such as MnS, Al2O3, (Al,Ca)-O, Nb(C,N), (Nb,Ti)(C,N), Ti(C,S) and MnS complex precipitates with these as nuclei. Hydrogen trapped by a relatively weak force around these inclusions is detected as quasi-diffusible hydrogen, so the fewer these inclusions there are, the more the delayed fracture resistance can be improved. To improve delayed fracture resistance to a high level, the fewer inclusions there are, the more likely it is that the number of inclusions will be 10 / mm 2 The inclusion group must be 5 pieces / mm 2 The inclusion group is preferably 0 pieces / mm 2 It is more preferable that:
[0062] Furthermore, the length of the major axis of a group of inclusions having one or more inclusion particles as specified in the present invention is 50 μm or more. A group of inclusions having a major axis length of 50 μm or more adversely affects delayed fracture resistance. When an inclusion group is composed of two or more inclusion particles, the length of the major axis of the inclusion particles that compose the inclusion group is 0.3 μm or more. The reason for focusing on inclusion particles with a major axis length of 0.3 μm or more is that inclusion particles smaller than 0.3 μm have little adverse effect on delayed fracture resistance even if they are aggregated. This is because the frequency of inclusion groups is low, and cracks are difficult to link and propagate when the size is less than that. The length of the major axis means the length of the inclusion particle in the rolling direction. When an inclusion group is composed of two or more inclusion particles, the shortest distance between the inclusion particles is 40 μm or less. Here, the shortest distance between inclusion particles refers to the shortest distance among the distances between two target inclusion particles, and can also be called the shortest interparticle distance.
[0063] By defining the inclusion group in this way, the inclusion group that affects the delayed fracture resistance property can be appropriately expressed for the inclusion group having one or more inclusion particles that satisfy condition (i), and the inclusion group based on this definition can be appropriately expressed for the unit area of the steel sheet (mm 2 ) can improve delayed fracture resistance. The shortest distance specified in condition (ii) applies to inclusion particles in a sector-shaped region of ±10° with respect to the rolling direction with the longitudinal end of the inclusion particle as the center point (if a part of the inclusion particle is included in the above region, it is applied). The shortest distance between particles is the shortest distance between points on the outer periphery of each particle. The shape and existence state of the inclusion particles constituting the inclusion group are not particularly limited, but in the present invention, they may be inclusion particles extending in the rolling direction or inclusions distributed in a dotted line in the rolling direction. "Inclusion particles distributed in a dotted line in the rolling direction" refers to inclusion particles consisting of two or more inclusion particles distributed in a dotted line in the rolling direction. "Distributed in a dotted line in the rolling direction" refers to a distribution state similar to that in which inclusions extending in the rolling direction are divided during cold rolling and distributed in a dotted line. Note that this is an explanation of the distribution state, and does not mean to be limited to those divided during cold rolling and distributed in a dotted line.
[0064] Furthermore, in the present invention, when measured by temperature rise analysis, the total amount of diffusible hydrogen released from room temperature to 350°C (hydrogen concentration H L ) is 0.30 mass ppm or less, and the amount of hydrogen released at 150°C to 350°C (total of semi-diffusible hydrogen) is the hydrogen concentration H H The total amount of hydrogen released from room temperature to 350°C (hydrogen concentration H L ) is the amount of hydrogen released at temperatures between 150 and 350°C, and the hydrogen concentration H H The total amount of hydrogen (H L ), diffusible hydrogen that is released at temperatures below 150°C when measured by temperature rise analysis is released into the atmosphere when the high-strength hot-dip galvanized steel sheet is left for about two weeks after production, and has a relatively small effect on delayed fracture resistance. On the other hand, the amount of hydrogen released at temperatures between 150°C and 350°C (hydrogen concentration (quasi-diffusible hydrogen concentration) H H ) measured immediately after manufacture does not decrease much when left at room temperature, and it has a large effect on delayed fracture resistance. Therefore, the amount of hydrogen released at temperatures between 150°C and 350°C (hydrogen concentration H HThe smaller the value of is, the better, and is preferably 0.15 ppm by mass or less, more preferably 0.10 ppm by mass or less, and even more preferably 0.05 ppm by mass or less. In the present invention, "room temperature" refers to 25°C.
[0065] Furthermore, the hot-dip galvanized steel sheet of the present invention has less than three uncoated defects in an area of 1 m × 1 m on the steel sheet surface, and has a beautiful surface appearance free of uncoated defects. Uncoated defects can be evaluated by visually observing the coating appearance of the hot-dip galvanized steel sheet, and the detailed method is as described in the examples below.
[0066] The thickness of the steel plate is not particularly limited, but is preferably 0.5 mm or more, and is preferably 3.2 mm or less.
[0067] ·Ingredient composition A preferred chemical composition of the substrate steel sheet (base steel sheet) will be described below. The substrate steel sheet (base steel sheet) targeted by this invention has a chemical composition comprising: C: 0.06% or more and 0.30% or less, Si: 0.01% or more and 3.00% or less, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (not including 0%), S: 0.0030% or less (not including 0%), sol. Al: 0.1% or less (not including 0%), N: 0.0070% or less (not including 0%), O: 0.0030% or less (not including 0%), or further contains one or more groups selected from the following groups A, B, C, D, E, F, G and H. Group A One or more selected from the following: Nb: 0.05% or less (excluding 0%), Ti: 0.08% or less (excluding 0%), V: 0.2% or less (excluding 0%), W: 0.15% or less (excluding 0%), Zr: 0.15% or less (excluding 0%) Group B One or more selected from the following: Cr: 1% or less (excluding 0%), Ni: 1% or less (excluding 0%), Cu: 1% or less (excluding 0%), Mo: 1% or less (excluding 0%), B: 0.005% or less (excluding 0%) Group C One or more selected from the following: Ca: 0.005% or less (excluding 0%), Mg: 0.005% or less (excluding 0%), REM: 0.005% or less (excluding 0%) Group D One or more selected from the following: Sn: 0.2% or less (excluding 0%), Sb: 0.2% or less (excluding 0%) Group E Ta: 0.10% or less (excluding 0%) F group One or more selected from the following: Te: 0.10% or less (excluding 0%), As: 0.10% or less (excluding 0%), Hf: 0.10% or less (excluding 0%) G group One or more selected from the following: Bi: 0.20% or less (excluding 0%), Pb: 0.20% or less (excluding 0%) H group One or more selected from the following: Zn: 0.10% or less (excluding 0%), Ge: 0.10% or less (excluding 0%), Sr: 0.10% or less (excluding 0%), Cs: 0.10% or less (excluding 0%) The reasons for including the above elements are as follows.
[0068] ·C: 0.06% or more and 0.30% or less C forms martensite, bainite, residual γ, and the like as a steel structure, and thereby has the effect of increasing the strength of steel and improving its workability. In order to obtain good workability while increasing strength, the C content is set to 0.06% or more. In order to obtain good workability while increasing strength, it is more preferable that the C content be 0.09% or more. On the other hand, in order to obtain good weldability, the C content is set to 0.30% or less. From the viewpoint of obtaining good weldability, the C content is preferably set to 0.25% or less.
[0069] ·Si: 0.01% or more and 3.00% or less Since silicon has a large effect of increasing the strength of steel through solid solution (solid solution strengthening ability) without significantly impairing workability, it is an effective element for achieving high strength in steel sheets. For this reason, the silicon content is set to 0.01% or more. On the other hand, if the Si content exceeds 3.00%, the hot rolling property and cold rolling property are significantly deteriorated, adversely affecting productivity. In addition, there is a possibility that the ductility of the steel sheet is deteriorated. For this reason, the Si content is set to 3.00% or less. From this viewpoint, the Si content is preferably 2.50% or less, and more preferably 2.00% or less.
[0070] ·Mn: 1.5% or more and 3.5% or less Mn is an element that strengthens steel through solid solution strengthening, improves hardenability, and promotes the formation of residual γ, bainite, and martensite. These effects are achieved by including 1.5% or more of Mn. For this reason, the Mn content is set to 1.5% or more. The Mn content is preferably set to 1.8% or more. On the other hand, if the Mn content exceeds 3.5%, the amount of inclusions such as MnS formed increases, deteriorating the delayed fracture resistance. Therefore, the Mn content is set to 3.5% or less. The Mn content is preferably set to 3.3% or less.
[0071] P: 0.1% or less (excluding 0%) By suppressing the P content, it is possible to prevent a decrease in weldability, and further to prevent P from segregating to grain boundaries, thereby preventing deterioration of ductility, bendability, and toughness. Furthermore, if a large amount of P is contained, the crystal grain size also becomes large by promoting ferrite transformation. For this reason, the P content is set to 0.1% or less. There is no particular lower limit for the P content, but due to production technology constraints, it is preferable that the P content be 0.001% or more.
[0072] S: 0.0030% or less (excluding 0%) The S content must be strictly controlled because it has a significant adverse effect on delayed fracture resistance through the formation of MnS, TiS, Ti(C,S), etc. In particular, MnS is elongated during hot rolling, and is crushed and elongated during cold rolling. In the final product, it may form inclusions reaching a length of 80 to 400 μm. In addition, if Nb(C,N), (Nb,Ti)(C,N), etc. remain in steel containing Nb and Ti during slab heating, MnS is formed by combining with them around them, which promotes the formation of inclusions with a length of 20 μm or more and less than 100 μm. Moreover, compared to Nb(C,N), etc., MnS covers the surroundings, which reduces the peel strength with the parent phase and may significantly worsen delayed fracture. In the case of the steel plate (thin steel plate) of the present invention, for example, when the thickness of the cast slab is about 180 to 250 mm and the thickness of the final product plate is 0.5 to 2.6 mm, the cumulative reduction amount is about 99%. In the case of thin steel plate, the elongation rate of the steel plate in the rolling direction reaches 5 to 10 times that of thick steel plate, so the adverse effect of MnS becomes even greater. In particular, in the shear end surface processed by punching, all areas in the plate thickness direction are exposed, so a huge group of inclusions is formed in the Mn segregation part in the plate thickness center. As a result, in combination with Mn segregation, it has a particularly adverse effect on the delayed fracture resistance property. In order to reduce the adverse effect of this group of inclusions, the S content needs to be 0.0030% or less. The S content is preferably 0.0020% or less, more preferably 0.0010% or less, and even more preferably 0.0003% or less. There is no particular limit to the lower limit of the S content, but due to constraints on production technology, the S content is preferably 0.0001% or more.
[0073] Sol.Al: 0.1% or less (excluding 0%) If the sol.Al content exceeds 0.1%, the cost increases. Therefore, the sol.Al content is set to 0.1% or less. There is no particular lower limit for the Al content, but since removing Al at the impurity level also leads to an increase in costs, it is preferable that the sol.Al content is set to 0.001% or more. Furthermore, since Al is thermodynamically very susceptible to oxidation, it oxidizes before Si and Mn, and has the effect of suppressing the oxidation of Si and Mn at the outermost layer of the steel sheet and promoting the oxidation of Si and Mn inside the steel sheet. This effect is obtained when the sol.Al content is 0.01% or more. Therefore, it is preferable that the sol.Al content is 0.01% or more.
[0074] N: 0.0070% or less (excluding 0%) N is an element that forms nitride and carbonitride inclusions such as TiN, (Nb,Ti)(C,N), and AlN in steel, and the delayed fracture resistance is deteriorated through the formation of these inclusions. Although the influence of these inclusions alone on delayed fracture is small, some of them become precipitation nuclei of MnS and are distributed in a dotted row with MnS to form a huge inclusion group, thereby deteriorating the delayed fracture resistance. In order to suppress the formation of such inclusion groups, the N content must be 0.0070% or less. The N content is preferably 0.005% or less, and more preferably 0.002% or less. There is no particular limit to the lower limit of the N content, but due to the constraints of production technology, the N content is preferably 0.0005% or more.
[0075] O: 0.0030% or less (excluding 0%) O is an element that forms oxide-based inclusions such as Al2O3, SiO2, CaO, MgO, (Al,Ca)-O, and (Si,Mn)-O in steel, and the generation of these inclusions deteriorates the delayed fracture resistance. In order to reduce such adverse effects on the delayed fracture resistance, the O content is set to 0.0030% or less. From the viewpoint of improving the delayed fracture resistance, the O content is more preferably set to less than 0.0020%. The lower limit of the O content is not particularly limited, but considering the lower limit currently available in industry, the O content is preferably set to 0.0005% or more.
[0076] Group A [one or more elements selected from Nb: 0.05% or less (excluding 0%), Ti: 0.08% or less (excluding 0%), V: 0.2% or less (excluding 0%), W: 0.15% or less (excluding 0%), and Zr: 0.15% or less (excluding 0%)] Nb, Ti, V, W, and Zr are all effective elements for increasing the strength of the base steel sheet (base steel sheet) and can be added as necessary. Of these elements in group A, Nb is an element that can obtain a fine structure even with a small amount of Nb, and can increase strength without impairing toughness.
[0077] Nb: 0.05% or less (excluding 0%) Nb contributes significantly to improving delayed fracture resistance as well as increasing strength through the refinement of prior γ grains, the refinement of the internal structure of martensite and bainite, the formation of fine precipitates that act as hydrogen trapping sites, and the formation of texture, even when added in small amounts. From this viewpoint, it is preferable to add 0.002% or more of Nb. The Nb content is more preferably 0.004% or more, and even more preferably 0.010% or more. On the other hand, if a large amount of Nb is contained, the amount of coarse Nb-based precipitates such as NbN, Nb(C,N), (Nb,Ti)(C,N) that remain in an insoluble state during slab heating in the hot rolling process increases, and MnS precipitates in combination with these precipitates, deteriorating the delayed fracture resistance. For this reason, when Nb is contained, the Nb content is set to 0.05% or less. The Nb content is preferably 0.04% or less, and more preferably 0.03% or less.
[0078] Ti: 0.08% or less (excluding 0%) Ti contributes significantly to high strength and delayed fracture resistance through the refinement of prior γ grains, the refinement of the internal structure of martensite and bainite, the formation of fine precipitates that become hydrogen trapping sites, and the formation of texture, even when added in small amounts. It also contributes to the improvement of castability. From this viewpoint, it is preferable that Ti is contained in an amount of 0.002% or more. The Ti content is more preferably 0.004% or more, and further preferably 0.010% or more. On the other hand, if Ti is contained in a large amount, the amount of Ti-based coarse precipitates such as Ti, N, Ti(C,N), Ti(C,S), TiS, etc. that remain in an insoluble state during slab heating in the hot rolling process increases, and MnS precipitates in combination with these precipitates, deteriorating the delayed fracture resistance. Therefore, when Ti is contained, the Ti content is set to 0.08% or less. The Ti content is preferably 0.05% or less, and more preferably 0.02% or less.
[0079] V: 0.2% or less (excluding 0%) A V content of 0.005% or more has the effect of improving strength, but from the viewpoint of preventing deterioration of delayed fracture resistance and increase in costs, if V is contained, the V content is set to 0.2% or less.
[0080] W: 0.15% or less (excluding 0%) The effect of improving strength can be obtained by including 0.005% or more of W. However, from the viewpoint of preventing deterioration of delayed fracture resistance and increase in costs, if W is included, the W content is set to 0.15% or less.
[0081] Zr: 0.15% or less (excluding 0%) A Zr content of 0.0005% or more provides the effect of improving strength, but from the viewpoint of preventing deterioration of delayed fracture resistance and increase in costs, if Zr is contained, the Zr content is set to 0.15% or less.
[0082] B group [one or more elements selected from Cr: 1% or less (excluding 0%), Ni: 1% or less (excluding 0%), Cu: 1% or less (excluding 0%), Mo: 1% or less (excluding 0%), Co: 1% or less (excluding 0%), and B: 0.005% or less (excluding 0%)] Cr, Ni, Cu, Mo, Co and B are all elements that improve the hardenability of steel sheet.
[0083] Cr: 1% or less (excluding 0%) When Cr is contained in an amount of 0.005% or more, the hardenability is improved and the balance between strength and ductility can be improved. However, from the viewpoint of preventing an increase in costs, if Cr is contained, the Cr content is set to 1% or less.
[0084] Ni: 1% or less (excluding 0%) The Ni content of 0.005% or more can promote the formation of the residual γ phase, but from the viewpoint of preventing an increase in costs, when Ni is contained, the Ni content is preferably 1% or less.
[0085] Cu: 1% or less (excluding 0%) Although the Cu content of 0.005% or more can promote the formation of the residual γ phase, from the viewpoint of preventing an increase in costs, when Cu is contained, the Cu content is set to 1% or less.
[0086] Mo: 1% or less (excluding 0%) When Mo is contained in an amount of 0.005% or more, the strength adjusting effect is obtained, and this effect is particularly enhanced when the Mo content is 0.05% or more. However, from the viewpoint of preventing an increase in costs, when Mo is contained, the Mo content is set to 1.0% or less.
[0087] Cobalt: 1% or less (excluding 0%) Co content of 0.001% or more improves the ultimate deformability of the steel sheet, and improves the stretch flangeability. In particular, the effect is enhanced when the Co content is 0.005% or more. However, from the viewpoint of preventing an increase in costs, when Co is contained, the Co content is set to 1% or less.
[0088] B: 0.005% or less (excluding 0%) B is an element effective in improving the hardenability of steel. In order to improve the hardenability, the B content is preferably 0.0003% or more, and more preferably 0.0005% or more. However, an excessive B content reduces formability, so when B is contained, the B content is set to 0.005% or less.
[0089] C group [one or more elements selected from Ca: 0.005% or less (excluding 0%), Mg: 0.005% or less (excluding 0%), and REM: 0.005% or less (excluding 0%)] Ca, Mg, and REM (rare earth elements) are all elements used to control the morphology of sulfides.
[0090] Ca: 0.005% or less (excluding 0%) When Ca is contained in an amount of 0.0005% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. From the viewpoint of obtaining good ductility, however, when Ca is contained, the Ca content is set to 0.005% or less.
[0091] Magnesium: 0.005% or less (excluding 0%) When Mg is contained in an amount of 0.0005% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, if Mg is contained, the Mg content is set to 0.005% or less.
[0092] REM: 0.005% or less (not including 0%) When REM is contained in an amount of 0.0005% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. From the viewpoint of obtaining good toughness, however, when REM is contained, the REM content is set to 0.005% or less. In the present invention, REM refers to scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanoids from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM content in the present invention is the total content of one or more elements selected from the above-mentioned REM. The REM is not particularly limited, but is preferably La and / or Ce.
[0093] D group [one or more elements selected from Sn: 0.2% or less (excluding 0%) and Sb: 0.2% or less (excluding 0%)] Sb and Sn are elements that suppress decarburization, denitrification, deboronization, etc., and are effective in suppressing a decrease in the strength of the steel sheet. Therefore, when Sb and Sn are contained, their respective contents are set to exceed 0%.
[0094] ·Sn: 0.2% or less Sn is an element that is effective in suppressing the deterioration of the strength of steel by suppressing denitrification, deboronization, etc., and in order to obtain such an effect, it is preferable to contain 0.002% or more. On the other hand, if Sn is contained in order to obtain good impact resistance, the Sn content is set to 0.2% or less.
[0095] ·Sb: 0.2% or less Sb can be added from the viewpoint of suppressing nitridation and oxidation of the steel sheet surface, or decarburization of a region of several tens of microns on the steel sheet surface caused by oxidation. Sb suppresses the nitridation and oxidation of the steel sheet surface, thereby preventing a decrease in the amount of martensite formed on the steel sheet surface, and improving the fatigue properties and surface quality of the steel sheet. To obtain such an effect, the Sb content is preferably 0.001% or more. On the other hand, when Sb is added to obtain good toughness, the Sb content is set to 0.2% or less.
[0096] Group E [Ta: 0.10% or less (excluding 0%)] Ta, like the elements in group A, is an effective element for increasing the strength of the base steel sheet, and can be added as necessary. Although the effect of improving strength can be obtained by adding Ta at 0.005% or more, from the viewpoint of preventing an increase in costs, if Ta is added, the Ta content is set to 0.10% or less.
[0097] F group [one or more elements selected from Te: 0.10% or less (excluding 0%), As: 0.10% or less (excluding 0%), and Hf: 0.10% or less (excluding 0%)] Te, As, and Hf, like the elements of group C, are all elements used to control the morphology of sulfides.
[0098] Te: 0.10% or less (excluding 0%) When Te is contained in an amount of 0.001% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, when Te is contained, the Te content is set to 0.10% or less.
[0099] As: 0.10% or less (excluding 0%) When As is contained in an amount of 0.001% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, if As is contained, the As content is set to 0.10% or less.
[0100] Hf: 0.10% or less (excluding 0%) When Hf is contained at 0.01% or more, the morphology of sulfides can be controlled and ductility and toughness can be improved. However, from the viewpoint of preventing an increase in costs, if Hf is contained, the Hf content is set to 0.10% or less.
[0101] Group G [one or more elements selected from Bi: 0.20% or less (excluding 0%) and Pb: 0.20% or less (excluding 0%)] Both Bi and Pb are elements that suppress grain boundary segregation and improve ductility and toughness. When Bi and Pb are contained, their respective contents must exceed 0%.
[0102] Bi: 0.20% or less (not including 0%) When Bi is contained at 0.001% or more, it is possible to suppress grain boundary segregation and improve ductility and toughness. Bi also has the effect of improving machinability and smoothness of cut end surfaces, and has the effect of improving delayed fracture resistance of cut surfaces. When Bi is contained, the Bi content is set to 0.10% or less from the viewpoint of preventing an increase in costs.
[0103] Pb: 0.20% or less (excluding 0%) The Pb content of 0.001% or more suppresses grain boundary segregation and improves ductility and toughness. Pb also has the effect of improving machinability and smoothness of cut edges, and improves delayed fracture resistance of cut edges. If Pb is contained, the Pb content is set to 0.10% or less to prevent an increase in costs.
[0104] H group [one or more elements selected from Zn: 0.10% or less (excluding 0%), Ge: 0.10% or less (excluding 0%), Sr: 0.10% or less (excluding 0%), Cs: 0.10% or less (excluding 0%)] Zn, Ge, Sr, and Cs are elements that increase strength without significantly affecting mechanical properties or surface quality. When Zn, Ge, Sr, and Cs are contained, their respective contents must exceed 0%.
[0105] Zn: 0.10% or less (excluding 0%) Even if Zn is contained in an amount of 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. From the viewpoint of preventing an increase in costs, if Zn is contained, the Zn content is set to 0.10% or less.
[0106] Ge: 0.10% or less (excluding 0%) Even if Ge is contained at 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. From the viewpoint of preventing an increase in costs, if Ge is contained, the Ge content is set to 0.10% or less.
[0107] Sr: 0.10% or less (excluding 0%) Even if the Sr content is 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. From the viewpoint of preventing an increase in costs, if Sr is contained, the Sr content is set to 0.10% or less.
[0108] Cs: 0.10% or less (excluding 0%) Even if the Cs content is 0.001% or more, it does not have a significant effect on mechanical properties or surface quality. To prevent an increase in costs, if Cs is contained, the Cs content is set to 0.10% or less.
[0109] Steel Sheet (Base Steel Sheet) The balance of the steel sheet other than the above-mentioned composition is Fe and unavoidable impurities.
[0110] ·Steel structure There are no particular limitations on the structure of the base steel sheet (underlying steel sheet), but in order to ensure a tensile strength of 780 MPa or more, it is preferable for the steel sheet structure to be as follows (steel structure in the range of 1 / 8 thickness to 3 / 8 thickness, centered on the 1 / 4 thickness position from the surface of the base steel sheet). That is, it is preferable that the total area ratio of martensite, bainite and retained austenite (retained γ) is 30% or more, thereby obtaining a base steel sheet having a tensile strength of 780 MPa or more.
[0111] Furthermore, by making the total area ratio of martensite, bainite and retained γ 50% or more, a base steel plate having a tensile strength of 980 MPa or more can be obtained, and by making the total area ratio of martensite, bainite and retained γ 70% or more, a base steel plate having a tensile strength of 1180 MPa or more can be obtained.
[0112] Furthermore, by setting the total area ratio of martensite, bainite and residual γ to 85% or more, a base steel sheet having a tensile strength of 1310 MPa or more can be obtained, and by setting the total area ratio of martensite, bainite and residual γ to 90% or more, a base steel sheet having a tensile strength of 1470 MPa or more can be obtained. In addition, in steels having a total area ratio of martensite, bainite and residual γ of 50% or more, particularly 90% or more, the hydrogen diffusion rate is significantly reduced and hydrogen tends to remain in the steel, but by adopting the manufacturing method of the present invention described above, it is possible to reduce quasi-diffusible hydrogen in the base steel sheet of the present invention.
[0113] In order to ensure a desired tensile strength TS, from the viewpoint of obtaining the total area ratio of martensite, bainite, and residual γ, it is particularly desirable to appropriately control the C content, Si content, Mn content, and annealing temperature. For example, in order to obtain a total area ratio of martensite, bainite, and residual γ of 90% or more, it is preferable that the C content is 0.17% or more, the Si content is 0.1% or more, the Mn content is 2.3% or more, and the annealing temperature (particularly the annealing temperature (holding temperature) in the second annealing step) is 820°C or more.
[0114] Here, the size and abundance of each structure are not particularly limited, but as an embodiment of the present invention, the following sizes and abundances can be exemplified. The aspect ratio is the ratio of the length of the major axis to the minor axis perpendicular to the major axis, the thickness is the length of the minor axis, and the circle equivalent diameter is the diameter when the area of each structure is taken as the area of a circle. Martensite includes both tempered martensite and fresh martensite. Tempered martensite has the effect of improving elongation flangeability, and fresh martensite has the effect of improving ductility.
[0115] Tempered martensite Aspect ratio ≦8, equivalent circle diameter ≦30μm Distribution density of carbides inside the structure: 0.10 to 12 pieces / μm 2 Fresh martensite and residual γ Lumpy: Aspect ratio ≦8, Equivalent circle diameter: 3~30μm Granular: Aspect ratio ≦8, Equivalent circle diameter: 0.40μm or more, less than 3μm Plate or film: aspect ratio over 8, thickness: 0.10 to 8μm Bainite Film or plate: aspect ratio >8, thickness ≤8μm Lumpy: aspect ratio ≦8, equivalent circle diameter ≦30μm Distribution density of carbides inside the structure: 0.10 to 6 particles / μm in all forms 2 ·carbide Granular: Aspect ratio ≦8, Equivalent circle diameter: 0.01μm or more, less than 0.40μm Film-like: aspect ratio greater than 8, equivalent circle diameter: 0.01 μm or more, less than 0.10 μm
[0116] As an embodiment of the hot-dip galvanized steel sheet and the manufacturing method thereof according to the present invention, the manufacturing method of the hot-dip galvanized steel sheet and the hot-dip galvanized steel sheet have been described above. According to the present invention, in a manufacturing method of hot-dip galvanized steel sheet, the shape and number of inclusions constituted by MnS, Al2O3, (Al,Ca)-O, Nb(C,N), (Nb,Ti)(C,N), Ti(C,S) contained in the steel sheet and MnS complex precipitated around the nucleus of the MnS inclusions and the inclusions constituted by these are controlled, and the steel sheet is annealed and cooled, and then hot-dip galvanized is performed. By optimizing the annealing and cooling atmosphere, it is possible to obtain a beautiful surface appearance without unplated areas, and to reduce the amount of hydrogen released from room temperature to 350°C (hydrogen concentration H L ) is suppressed to 0.30 mass ppm or less, and the amount of hydrogen released at 150°C to 350°C (hydrogen concentration H H) to 0.20 ppm by mass or less, thereby making it possible to produce a hot-dip galvanized steel sheet having even higher levels of excellent delayed fracture resistance. In addition, in the present invention, by carrying out an oxidation treatment before the annealing, and further carrying out the annealing under more limited conditions, and by carrying out a reheating treatment in a specific atmosphere after plating, it is possible to produce a hot-dip galvanized steel sheet having even higher levels of excellent plating appearance and delayed fracture resistance. EXAMPLES
[0117] The steel having the composition shown in Table 1 was refined under the conditions shown in Tables 2 to 5 to obtain a 200 mm thick slab, which was then reheated and hot rolled under the conditions shown in Tables 2 to 6. The hot rolling was adjusted so that the cumulative reduction in the temperature range of 950°C or higher was 95%, and the final plate thickness was 2.8 mm. The finishing rolling temperature in the hot rolling was 850°C, and the plate was cooled to 500°C at a cooling rate of 50°C / s, and then wound into a coil. Thereafter, the plate was water-cooled in the coiled state for 10 seconds, and then allowed to cool to room temperature. The hot-rolled steel sheet thus produced was pickled, and then cold-rolled to a thickness of 1.4 mm at a reduction of 50%. The cumulative reduction below 950°C, including cold rolling, was 86%. The cold-rolled steel sheets manufactured as described above were annealed under the conditions shown in Tables 2 to 4 and 6 in a continuous hot-dip galvanizing line (CGL) equipped with an all-radiant tube (ART) type annealing furnace, and then hot-dip galvanized (coating composition: Zn-0.2 mass% Al) was applied, and the coating weight per side was adjusted to 30 to 70 g / m by gas wiping. 2 Then, except for No. 89, the steels were subjected to an alloying treatment.
[0118] [Table 1]
[0119] Moreover, examples in which the cooling step was divided into two steps (first cooling step and second cooling step) are shown in Tables 3 and 6. Similarly, Table 4 shows an example in which a reheating treatment was carried out after plating and alloying treatment. The primary cooling end temperature (final holding temperature (steel sheet temperature) in the first cooling step) was 650°C for Nos. 100 to 128, and was varied from 600 to 640°C for Nos. 176 to 178 shown in Table 6.
[0120] Separately from the above-mentioned examples, in a CGL having a direct-fire annealing furnace (DFF-type annealing furnace) with a direct flame burner, a steel sheet was oxidized and annealed under the conditions shown in Table 5, and then hot-dip galvanized (coating composition: Zn-0.2 mass% Al) was applied, and the coating weight per side was adjusted to 30 to 70 g / m by gas wiping. 2 Then, the alloying treatment was carried out. No. 152 (Table 5) is an example in which oxidation treatment was performed at a constant temperature, and the retention time (treatment time) of the oxidation treatment was 8 seconds. In the other examples (Nos. 150, 151, 153 to 175), oxidation treatment was performed during temperature rise, and the temperature rise rate of this oxidation treatment was in the range of 5 to 20°C / s.
[0121] The hot-dip galvanized steel sheets thus obtained were subjected to measurement of the amount of diffusible hydrogen in the steel sheets and evaluation of the coating appearance and delayed fracture resistance by the following measurement and evaluation methods. The results are shown in Tables 2 to 6 together with the manufacturing conditions. Here, in the oxidation treatment of the examples in Table 5, the "oxidation start temperature" is the entry strip temperature of the oxidation zone in the heating zone of a DFF-type annealing furnace, the "oxidation end temperature" is the exit strip temperature of the oxidation zone, and the oxygen concentration is the oxygen concentration in the oxidation zone. Therefore, the range from the oxidation start temperature to the oxidation end temperature is the oxidation treatment temperature. Also, the "oxidation temperature range" is the temperature range over which the steel sheet rises in temperature in the oxidation zone (the temperature range from the oxidation start temperature to the oxidation end temperature), and the "maximum steel sheet temperature" is the maximum temperature reached in the heating zone of a DFF-type annealing furnace. Therefore, when the "maximum steel sheet temperature" is higher than the "oxidation end temperature", the steel sheet is further heated in a non-oxidizing atmosphere in the zone next to the oxidation zone (a zone that is not an oxidation zone), and the maximum temperature reached in the zone next to the oxidation zone is the "maximum steel sheet temperature".
[0122] [Table 2-1]
[0123] [Table 2-2]
[0124] [Table 3]
[0125] [Table 4]
[0126] [Table 5]
[0127] [Table 6]
[0128] - Measurement of hydrogen content in steel sheets (hydrogen analysis method) A rectangular test piece with a major axis length of 30 mm and a minor axis length of 5 mm was taken from the center of the width of the hot-dip galvanized steel sheet, the zinc plating layer of the test piece was removed with a router, and immediately subjected to hydrogen analysis using a thermal desorption analyzer under conditions of an analysis start temperature of 25°C, an analysis end temperature of 400°C, and a heating rate of 200°C / hour. The amount of released hydrogen (mass ppm / min), which is the amount of hydrogen released from the test piece surface at each temperature, was measured. The total amount of released hydrogen from room temperature (25°C) to 350°C was defined as the hydrogen concentration H L The total amount of hydrogen released from 150℃ to 350℃ is the hydrogen concentration H H It was calculated as:
[0129] Here, the hydrogen concentration in the steel H LThe hydrogen concentration in steel is 0.05 mass ppm or less, which is excellent (◎+), between 0.05 mass ppm and 0.10 mass ppm or less, excellent (◎), between 0.10 mass ppm and 0.20 mass ppm or less, good (〇), and between 0.20 mass ppm and 0.30 mass ppm or less, fair (△). L When the content exceeds 0.30 ppm by mass, the delayed fracture resistance is often deteriorated, and therefore, when the content exceeds 0.30 ppm by mass, the content is rated as poor (×).
[0130] In addition, the hydrogen concentration in the steel, H H The hydrogen concentration in steel is 0.05 mass ppm or less, which is excellent (◎+), between 0.05 mass ppm and 0.10 mass ppm or less, excellent (◎), between 0.10 mass ppm and 0.15 mass ppm or less, good (〇), and between 0.15 mass ppm and 0.20 mass ppm or less, fair (△). H When the content exceeds 0.15 ppm by mass, the delayed fracture resistance is often deteriorated, and therefore, when the content exceeds 0.15 ppm by mass, the content is rated as poor (×).
[0131] ·Evaluation of plating appearance The appearance of the plating on hot-dip galvanized steel sheets was visually observed, and those without any patterns or irregularities were rated as excellent "◎". For those with patterns or irregularities, SEM observation of the relevant areas at a magnification of 50x determined that areas not covered by zinc plating over an area of 1.0mm x 1.0mm or more on the steel sheet were uncoated defects, and 3D shape measurement at 10x determined that irregularities over an area of 0.5mm x 0.5mm or more on the steel sheet with a maximum height of 5μm or more compared to the average height of the surrounding area were rated as pressure scratches. More specifically, a non-galvanized defect refers to an area of 1.0 mm x 1.0 mm or more where the zinc plating is not coated and which is observed in a darker contrast than the zinc plating coated area when a backscattered electron image is observed using an SEM at an accelerating voltage of 15 kV and a magnification of 50 times. Even if patterns or unevenness were observed, those without any uncoated defects were rated as good (○+), and those with three or more uncoated defects within a 1m x 1m area on the steel sheet surface were rated as poor (×). Also, those without any uncoated defects but with marks caused by picking up the rolls or a sign of such marks, such as a V-shaped scale pattern in the sheet running direction, or those with less than three uncoated defects within a 1m x 1m area on the steel sheet surface were rated as passing (○), although not good (○+).
[0132] Tensile Test A JIS Z2241 No. 5 test piece was taken from the hot-dip galvanized steel sheet in the direction perpendicular to the rolling direction (so that the sheet width direction was the tensile direction), and a tensile test was performed on this test piece in accordance with JIS Z2241 (2011) to measure the tensile strength (TS).
[0133] Observation and measurement of the substrate steel sheet structure (base steel sheet structure) The total area ratio of martensite, bainite and retained austenite (retained γ) in the substrate steel sheet structure (base steel sheet structure) was measured as follows. A sample was cut out so that the cross section (L cross section) parallel to the rolling direction of the steel sheet and parallel to the sheet thickness direction was the observation surface, and the observation surface of this sample was polished with diamond paste, and then finish-polished with alumina. Next, the observation surface of the sample was etched with 3 vol% nital to reveal the structure. The observation position was set to 1 / 4 of the sheet thickness on this sample observation surface, and five fields of view were observed at a magnification of 3000 times using an SEM. It was determined that the steel structure was observed in the range of 1 / 8 to 3 / 8 thickness, centered on the 1 / 4 thickness position from the surface of the base steel sheet. The total area of martensite, bainite and retained γ was calculated from the obtained structural images, and the area ratio was calculated by dividing this total area by the measured area for five fields of view, and the average of these values was taken as the total area ratio of martensite, bainite and retained γ. The discrimination of martensite, bainite, retained γ and other microstructures was performed as follows. Martensite There are two types of martensite: tempered martensite and fresh martensite. Tempered martensite Tempered martensite is a gray or dark gray area close to black in SEM photographs. Tempered martensite has a blocky morphology with boundaries at the interfaces with other structures such as prior gamma grain boundaries and ferrite. However, tempered martensite may contain other structures such as bainite inside and have a concave shape. Tempered martensite contains many carbides inside, but depending on the plane orientation, there may be only a small amount of carbides. Fresh martensite Fresh martensite is the grey or white area in the SEM photograph. Fresh martensite is in the form of blocks, granules, plates, or films and does not contain carbides. Bainite Bainite is the dark gray area in the SEM photograph. Bainite is in the form of a film, a plate, or a mass formed by some or all of these adjacent areas being connected, and contains a small amount of carbides inside. Bainite also includes carbides that have been coarsened by tempering after formation. ·Residual austenite (retained γ) The retained γ is an area that has the same color and morphology as the above-mentioned fresh martensite. Note that the retained γ and fresh martensite cannot be distinguished by SEM.
[0134] In order to ensure the strength of the steel plate, it is necessary to control the total area ratio of the martensite, bainite, and retained γ described above, but the balance may include the structures shown below, but is not limited thereto. Ferrite Ferrite is the black area in the SEM photograph. Ferrite has a blocky morphology and contains almost no carbides. Bainitic ferrite contains almost no carbides inside and has similar mechanical properties to ferrite, so it belongs to the ferrite category. Ferrite may contain either or both granular and blocky fresh martensite, and either or both granular and blocky retained gamma. Fresh martensite and retained gamma contained in ferrite are not included in the area ratio of ferrite, but are treated as the area ratio of fresh martensite or retained gamma. ·carbide Carbides are the white regions in SEM photographs. Carbides are in the form of grains or films. Carbides form finely mainly inside ferrite, martensite, and bainite, but the area ratio of these is small and can be ignored, so the area ratio of carbides is not excluded from the area ratio of each structure, but is included in it. - Organizations other than those mentioned above In addition to the above, nitrides such as TiN, carbonitrides such as (Nb,Ti)(C,N), sulfides such as MnS and CaS, and oxides such as Al2O3 and SiO2 may also be contained at a total area ratio of a few percent. As the area ratios of these are small and can be ignored, these area ratios are included in the area ratios of each structure that contains them. In some cases, pearlite may also be included. In the case of pearlite, the area ratio of pearlite is calculated separately.
[0135] Observation and measurement of inclusions and inclusion groups In the substrate steel sheet, the number of inclusions per unit area satisfying the following conditions (i) and (ii) was determined by the following measurement method. (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When an inclusion group is composed of two or more of the above-mentioned inclusion particles, the major axis length of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less. 1mm of inclusion group 2The number density per mm was measured in the area of t / 5 to 4t / 5 (t is the thickness of the steel sheet) from the surface of the steel sheet without corrosion after polishing the L section (vertical section parallel to the rolling direction), that is, in the area from the 1 / 5 thickness position from the surface to the 1 / 5 thickness position on the back surface side, including the center of the thickness. 2 Approximately 100 fields of view were photographed consecutively with an SEM, and the number of inclusion groups was counted from the SEM photographs. Measurements were performed in the 1 / 5t to 4 / 5t region from the surface of the steel plate because inclusion groups are less common on the surface layer of the steel plate and more common near the center of the plate thickness, resulting in initial cracks initiating near the center of the plate thickness. The photographs were enlarged 1000 times for measurement. Since the inclusion groups are generated in a thin film-like form, they are difficult to identify when observed on a surface parallel to the rolled surface or with an optical microscope, and it is also difficult to accurately measure their length.
[0136] Here, the SEM image was a backscattered electron image, and the magnification for taking the image was preferably 1000 times. However, when it was difficult to accurately grasp the size of the inclusion particles or the distance between the inclusion particles, each inclusion particle was magnified 5000 times as appropriate, and a visual field equivalent to that of 1000 times was measured to evaluate the above-mentioned inclusion group by image.
[0137] As described above, the shortest distance between inclusion particles is the surface-to-surface distance, and means the surface-to-surface distance that can be obtained from this image. Also, the measurement direction of the shortest distance is limited to the rolling direction or within the range of rolling direction ±10 degrees, as described above. Furthermore, when an inclusion group is composed of two or more inclusion particles, the total length (length of the major axis) of the inclusion group in the rolling direction is the length in the rolling direction between the outer ends in the rolling direction of the inclusion particles located at both ends of the inclusion group in the rolling direction. Furthermore, when an inclusion group is composed of one inclusion particle, the total length of the inclusion group in the rolling direction is the length of this inclusion particle in the rolling direction.
[0138] Furthermore, the individual inclusion particles that make up this group of inclusions are mainly sulfides of Mn, Ti, Zr, Ca, and REM, oxides of Al, Ca, Mg, Si, and Na, nitrides of Ti, Zr, Nb, and Al, and carbides of Ti, Nb, Zr, and Mo. Most of these inclusions are formed during the casting process and existed in an undissolved state when the slab was heated thereafter, and the rest are redeposited in combination with or adjacent to them during the subsequent hot rolling and coiling.
[0139] -Evaluation of delayed fracture resistance A rectangular test piece with a major axis length of 100 mm and a minor axis length of 20 mm was taken from the hot-dip galvanized steel sheet in the direction perpendicular to the rolling direction, and a punched hole with a diameter of 15 mm and a clearance of 14.0% was formed at the center of the major and minor axes of the test piece. The clearance was previously set to about 12.5%, but in light of the recent trend toward stricter quality standards for delayed fracture resistance, a more stringent condition was adopted than before. The test piece was subjected to a tensile test, and the delayed fracture resistance was evaluated based on the presence or absence of delayed fracture from the punched hole. In order to prevent the release of diffusible hydrogen in the steel due to changes over time, the time from taking the rectangular test piece from the hot-dip galvanized steel sheet to starting the delayed fracture tensile test (tensile speed 10 mm / min) was set to within 10 minutes. The loading time of the tensile test was set to a maximum of 100 hours, and the maximum stress at which no cracks (here, cracks mean fractures when tensile stress is applied) did not occur after 100 hours of loading was set as the limit stress, and the delayed fracture resistance was evaluated by the ratio of the limit stress to the yield stress. The evaluation criteria for delayed fracture resistance are as follows: when the critical stress / yield stress is 1.10 or more, it is excellent (◎), when it is less than 1.10 and 1.05 or more, it is good (〇), when it is less than 1.05 and 1.00 or more, it is not good (○) but acceptable (△), and when it is less than 1.00, it is poor (×). Note that the delayed fracture resistance evaluated in the delayed fracture test is generally lower (disadvantageous) for steel plates with higher strength.
[0140] According to Tables 1 to 6, the hot-dip galvanized steel sheets of the examples of the present invention have high strength and a beautiful surface appearance without uncoated areas, and also have excellent delayed fracture resistance.
Claims
1. In mass percent, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and 3.00% or less, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%) S: 0.0030% or less (excluding 0%), sol. Al: 0.1% or less (excluding 0%), N: 0.0070% or less (excluding 0%), O: Contains 0.0030% or less (excluding 0%), Or even more so: Contains one or more groups selected from the following groups A, B, C, D, E, F, G, and H, Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the following: Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following: Group C Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more selected from the following: Group D Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following: G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following: H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following: A base steel sheet having a composition with the balance being Fe and unavoidable impurities; A zinc-based plating layer is formed on the surface of the base steel sheet, Furthermore, the inclusion group contained in the base steel sheet satisfies the following conditions (i) and (ii), and the inclusion group has a density of 10 pieces / mm 2 is as follows: The base steel sheet has an amount of hydrogen released from room temperature to 350°C of 0.30 ppm by mass or less, and an amount of hydrogen released from 150 to 350°C of 0.20 ppm by mass or less, Within an area of 1 m x 1 m on the steel sheet surface, there are less than three uncoated defects; A hot-dip galvanized steel sheet having a tensile strength of 780 MPa or more. (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When the inclusion group is composed of two or more of the inclusion particles, the length of the major axis of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less.
2. 2. The hot-dip galvanized steel sheet according to claim 1, wherein the amount of hydrogen released from the base steel sheet at from room temperature to 350°C is 0.20 ppm by mass or less, and the amount of hydrogen released at from 150 to 350°C is 0.15 ppm by mass or less.
3. 3. The hot-dip galvanized steel sheet according to claim 1, wherein the base steel sheet has a total area ratio of martensite, bainite and retained austenite of 30% or more and a tensile strength of 780 MPa or more.
4. 3. The hot-dip galvanized steel sheet according to claim 1, wherein the base steel sheet has a total area ratio of martensite, bainite and retained austenite of 50% or more and a tensile strength of 980 MPa or more.
5. 3. The hot-dip galvanized steel sheet according to claim 1, wherein the base steel sheet has a total area ratio of martensite, bainite and retained austenite of 70% or more and a tensile strength of 1180 MPa or more.
6. 3. The hot-dip galvanized steel sheet according to claim 1, wherein the base steel sheet has a total area ratio of martensite, bainite and retained austenite of 85% or more and a tensile strength of 1,310 MPa or more.
7. 3. The hot-dip galvanized steel sheet according to claim 1, wherein the base steel sheet has a total area ratio of martensite, bainite and retained austenite of 90% or more and a tensile strength of 1470 MPa or more.
8. The hot-dip galvanized steel sheet according to claim 1 or 2, wherein the zinc-based plating layer is a galvannealed layer.
9. A method for producing a hot-dip galvanized steel sheet, comprising annealing a base steel sheet and then applying hot-dip galvanizing, The base steel sheet comprises, in mass%, C: 0.06% or more and 0.30% or less, Si: 0.01% or more and 3.00% or less, Mn: 1.5% or more and 3.5% or less, P: 0.1% or less (excluding 0%) S: 0.0030% or less (excluding 0%), sol. Al: 0.1% or less (excluding 0%), N: 0.0070% or less (excluding 0%), O: Contains 0.0030% or less (excluding 0%), Or even more so: Contains one or more groups selected from the following groups A, B, C, D, E, F, G, and H, Group A Nb: 0.05% or less (excluding 0%) Ti: 0.08% or less (excluding 0%) V: 0.2% or less (excluding 0%) W: 0.15% or less (excluding 0%) Zr: 0.15% or less (excluding 0%), one or more selected from the following: Group B Cr: 1% or less (excluding 0%) Ni: 1% or less (excluding 0%) Cu: 1% or less (excluding 0%) Mo: 1% or less (excluding 0%) Co: 1% or less (excluding 0%) B: 0.005% or less (excluding 0%), one or more selected from the following: Group C Ca: 0.005% or less (excluding 0%) Mg: 0.005% or less (excluding 0%) REM: 0.005% or less (excluding 0%), one or more selected from the following: Group D Sn: 0.2% or less (excluding 0%) Sb: 0.2% or less (excluding 0%), one or more selected from the following: Group E Ta: 0.10% or less (excluding 0%) F group Te: 0.10% or less (excluding 0%) As: 0.10% or less (excluding 0%) Hf: 0.10% or less (excluding 0%), one or more selected from the following: G group Bi: 0.20% or less (excluding 0%) Pb: 0.20% or less (excluding 0%), one or more selected from the following: H group Zn: 0.10% or less (excluding 0%) Ge: 0.10% or less (excluding 0%) Sr: 0.10% or less (excluding 0%) Cs: 0.10% or less (excluding 0%), one or more selected from the following: The balance is Fe and unavoidable impurities. Furthermore, the inclusion group contained in the base steel sheet satisfies the following conditions (i) and (ii), and the inclusion group has a density of 10 pieces / mm 2 is as follows: A first annealing process in which the base steel sheet is held at a holding temperature of 650°C to 950°C for 20s to 150s in an atmosphere with a dew point of -55°C to +30°C and a hydrogen concentration of 8.0% by volume to 25% by volume; A second annealing step of holding the base steel sheet that has been subjected to the first annealing step at a holding temperature of 700°C to 950°C for 30 s to 300 s in an atmosphere with a dew point of -50°C to +30°C and a hydrogen concentration of 0.2 vol% to less than 8.0 vol%; a cooling step of cooling the base steel sheet that has been subjected to the second annealing step from the holding temperature of 700° C. or more and 950° C. or less in the second annealing step to a temperature of 150° C. or more and 550° C. or less at an average cooling rate of 3 to 300° C. / s in an atmosphere having a dew point of −20° C. or less and a hydrogen concentration of 0.2 vol.% or more and 25 vol.% or less; a hot-dip galvanizing process for performing a hot-dip galvanizing treatment on the base steel sheet after the cooling process to form a zinc-based plating layer on the surface of the base steel sheet; Including, The substrate steel sheet has an amount of hydrogen released from room temperature to 350°C of 0.30 ppm by mass or less and an amount of hydrogen released from 150 to 350°C of 0.20 ppm by mass or less, has less than 3 uncoated defects within an area of 1 m x 1 m on the steel sheet surface, and has a tensile strength of 780 MPa or more. (conditions) (i) The length of the major axis of an inclusion group having one or more inclusion particles is 50 μm or more. (ii) When the inclusion group is composed of two or more of the inclusion particles, the length of the major axis of one inclusion particle is 0.3 μm or more, and the shortest distance between the inclusion particles is 40 μm or less.
10. The base steel sheet before the first annealing step is 2 The method for producing a hot-dip galvanized steel sheet according to claim 9, further comprising an oxidation treatment step of performing an oxidation treatment at a temperature of 400° C. or higher and 900° C. or lower in an atmosphere containing 1000 ppm by volume or more of
11. 11. The method for producing a hot-dip galvanized steel sheet according to claim 9 or 10, further comprising a reheating treatment step of holding the steel sheet at a temperature of 200° C. or higher and 450° C. or lower and in an atmosphere having a hydrogen concentration of 15 vol% or lower for a time of 5 s or higher and 600 s or lower after the hot-dip galvanized treatment, and then cooling the steel sheet.
12. The method for producing a hot-dip galvanized steel sheet according to claim 9 or 10, wherein the atmosphere in the second annealing step has a hydrogen concentration of less than 5.0 vol %.
13. The method for producing a hot-dip galvanized steel sheet according to claim 11, wherein the atmosphere in the second annealing step has a hydrogen concentration of less than 5.0 vol%.
14. The cooling step includes: a first cooling step in which the base steel sheet that has been subjected to the second annealing step is cooled in an atmosphere having a dew point of −20° C. or lower and a hydrogen concentration of 0.2 vol.% or higher and less than 8.0 vol.% through a temperature range from a holding temperature of 700° C. or higher and 950° C. or lower in the second annealing step to a steel sheet temperature of 650° C. or lower over a period of 10 s or more at an average cooling rate of 3° C. / s or higher and 25° C. / s or lower; a second cooling step of cooling the base steel sheet that has been subjected to the first cooling step in an atmosphere having a dew point of −20° C. or less and a hydrogen concentration of 8.0 vol.% or more and 25 vol.% or less, from 600° C. to a temperature of 150° C. or more and 550° C. or less at an average cooling rate of 10° C. / s or more; The method for producing a hot-dip galvanized steel sheet according to claim 9 or 10, comprising:
15. The cooling step includes: a first cooling step in which the base steel sheet that has been subjected to the second annealing step is cooled in an atmosphere having a dew point of −20° C. or lower and a hydrogen concentration of 0.2 vol.% or higher and less than 8.0 vol.% through a temperature range from a holding temperature of 700° C. or higher and 950° C. or lower in the second annealing step to a steel sheet temperature of 650° C. or lower over a period of 10 s or more at an average cooling rate of 3° C. / s or higher and 25° C. / s or lower; a second cooling step of cooling the base steel sheet that has been subjected to the first cooling step in an atmosphere having a dew point of −20° C. or less and a hydrogen concentration of 8.0 vol.% or more and 25 vol.% or less, from 600° C. to a temperature of 150° C. or more and 550° C. or less at an average cooling rate of 10° C. / s or more; The method for producing a hot-dip galvanized steel sheet according to claim 11, comprising:
16. The cooling step includes: a first cooling step in which the base steel sheet that has been subjected to the second annealing step is cooled in an atmosphere having a dew point of −20° C. or lower and a hydrogen concentration of 0.2 vol.% or higher and less than 8.0 vol.% through a temperature range from a holding temperature of 700° C. or higher and 950° C. or lower in the second annealing step to a steel sheet temperature of 650° C. or lower over a period of 10 s or more at an average cooling rate of 3° C. / s or higher and 25° C. / s or lower; a second cooling step of cooling the base steel sheet that has been subjected to the first cooling step in an atmosphere having a dew point of −20° C. or less and a hydrogen concentration of 8.0 vol.% or more and 25 vol.% or less, from 600° C. to a temperature of 150° C. or more and 550° C. or less at an average cooling rate of 10° C. / s or more; The method for producing a hot-dip galvanized steel sheet according to claim 12, comprising:
17. The cooling step includes: a first cooling step in which the base steel sheet that has been subjected to the second annealing step is cooled in an atmosphere having a dew point of −20° C. or lower and a hydrogen concentration of 0.2 vol.% or higher and less than 8.0 vol.% through a temperature range from a holding temperature of 700° C. or higher and 950° C. or lower in the second annealing step to a steel sheet temperature of 650° C. or lower over a period of 10 s or more at an average cooling rate of 3° C. / s or higher and 25° C. / s or lower; a second cooling step of cooling the base steel sheet that has been subjected to the first cooling step in an atmosphere having a dew point of −20° C. or less and a hydrogen concentration of 8.0 vol.% or more and 25 vol.% or less, from 600° C. to a temperature of 150° C. or more and 550° C. or less at an average cooling rate of 10° C. / s or more; The method for producing a hot-dip galvanized steel sheet according to claim 13, comprising:
18. The method for producing a hot-dip galvanized steel sheet according to claim 9 or 10, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
19. The method for producing a hot-dip galvanized steel sheet according to claim 11, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
20. The method for producing a hot-dip galvanized steel sheet according to claim 12, further comprising, after the hot-dip galvanizing step, an alloying treatment step of alloying the base steel sheet and the zinc-based plating layer.
Citation Information
Patent Citations
Hot stamp molded product and steel sheet for hot stamping
WO2021106936A1
Steel sheet and manufacturing method therefor
WO2021251276A1
Hot-dip galvanized steel sheet and method for producing same, and member
WO2022270053A1
Manufacture of zinc plated steel sheet
JP1979130443A
Method and device for x-ray diffraction
JP1983011841A